[Record not in use]
An output of the EdTech Hub, https://edtechhub.org
Keywords: _hide; _r:AddedByZotZen

[Record not in use]
An output of the EdTech Hub, https://edtechhub.org
Keywords: _hide; _r:AddedByZotZen

[Record not in use]
An output of the EdTech Hub, https://edtechhub.org
Keywords: _hide; _r:AddedByZotZen

Record not in use
An output of the EdTech Hub, https://edtechhub.org/
Keywords: _r:AddedByMyEducationEvidence

[unavailable]
Keywords: _DOILIVE; _EdTechHub_Output; _hide; _zenodoETH

[unavailable]
Keywords: _DOILIVE; _EdTechHub_Output; _MELA_seen; _cover:v2; _hide; _zenodoETH

Learning, Marginalization, and Improving the Quality of Education in Low-Income Countries - Castillo, Nathan; Adam, Taskeen; Haßler, Björn
Keywords: _EdTechHub_Output; _MELA_seen; _cover:analysis:nopdf; dode_eth-src-eth; dode_eth-trf2-dode

Recommendations report for technology and CPD for secondary school leaders and teachers in Sierra Leone - Lurvink, Anne-Fleur; Haßler, Björn (EdTech Hub)
An output of the EdTech Hub, https://edtechhub.org/
Keywords: _comingsoon; _r:AddedByMyEducationEvidence

Learning continuity in response to Pakistan’s 2022 floods: Policy brief - Mazari, Haani; Baloch, Imdad; Thinley, Sangay; Radford, Kate; Perry, Freya; Kaye, Tom (EdTech Hub)
An output of the EdTech Hub, https://edtechhub.org
Keywords: _r:AddedByZotZen

Education in Emergencies: A Rapid Evidence Review - Mitchell, Joel; Ashlee, Amy; Clericetti, Giulia; Gladwell, Jessica; Torrance, Rebecca (EdTech Hub, 2020)
Keywords: _DOILIVE; _EdTechHub_Output; _MELA_seen; _cover:v3; _zenodoETH

Cost-Effective EdTech Paper 3 - Mitchell, Joel; D'Rozario, Jonny (EdTech Hub)
An output of the EdTech Hub, https://edtechhub.org
Keywords: _comingsoon; _r:AddedByZotZen

Great buy or just low cost? Lessons on cost-effectiveness from messaging interventions in West Africa - Mitchell, Joel; Mukankusi, Aimée; D'Rozario, Jonny (EdTech Hub)
An output of the EdTech Hub, https://edtechhub.org/
Keywords: _comingsoon; _r:AddedByMyEducationEvidence

Video Pilot for TLC Facilitators: A research plan to support Teacher Learning Circle facilitators in Malawi's National Numeracy Programme through video modelling - Plaut, Daniel; Kanyoza, Charity (EdTech Hub)
An output of the EdTech Hub, https://edtechhub.org/
Keywords: _comingsoon; _r:AddedByMyEducationEvidence

Sierra Leone TCPD Sandbox Report - Tanweer, Rabia; Plaut, Daniel; McBurnie, Chris (EdTech Hub)
An output of the EdTech Hub, https://edtechhub.org
Keywords: _r:AddedByZotZen

Nudge Messaging and School Attendance in Ghana: Determining the Impact of Tailored Message Characteristics - Zhao, Annette; D'Rozario, Jonny; Kably, Nathan; Jayasinghe, Neema; Mukankusi, Aimée
An output of the EdTech Hub, https://edtechhub.org/
Keywords: _comingsoon; _r:AddedByMyEducationEvidence

144155524.pdf

16809eed0a.pdf

2014-02-14_Learning to Improve Learning Synthesis for Publishing_Edited_0.pdf

2021ISCReducedSyllabusXII-ECONOMICS.pdf

32947_Chapter1.pdf

6811.pdf

7taps mobile-first microlearning
7taps is a free browser-based authoring tool to create, deliver and track mobile-first microlearning experiences.

A comparison of smartphone and paper data-collection tools in the Burden of Obstructive Lung Disease (BOLD) study in Gezira state, Sudan | PLOS ONE

A lifeline to learning: Leveraging technology to support education for refugees - World (UNESCO)
English Analysis on World about Education, Children and Refugees; published on 26 Mar 2018 by UNESCO
Keywords: Google Scholar/ refugee education technology; Overarching paper; RER theme_pedagogies and modalities; RER_supporting educators

a2_-_mad_-_esp_fr.pdf

A_Systems_Approach_to_Educational_Testin.doc

ABC

About Our Organization (Jusoor)
Jusoor is a US 501c3 NGO of Syrian expatriates supporting the country’s development and helping Syrian youth realize their potential through programs in the fields of education, career development, and global community engagement. As a community of Syrians living around the world working together to launch programs that benefit the Syrian community inside and outside Syria. We are committed to…Read More →

About the Learning Passport
The Learning Passport is an Online, Mobile, and Offline tech platform enabling high quality, flexible learning

Abracadabra (ABRA) - re-grant | Projects
Project: Abracadabra (ABRA) - re-grant, Testing an online and a paper based version of a balanced approach to reading.

African Women in EdTech (WAKE)

Agency for the Development of Educational Management (ADEM)

AHHA Education Timor Leste (AHHA Education Timor Leste)
Keywords: ⛔ No INSPIRE recid found

amagoh3dec2008jag2rev1.pdf

Aprender a Ler (ApaL)

Arifu

ASER_National_2019.pdf

ASReview - Active learning for Systematic Reviews (ASReview)
Our software ASReview is designed to accelerate the step of screening abstracts and titles with a minimum of papers to be read.
Keywords: _Added-ailr-2024

Assistive Technology in the African Region: Results of an Online Rapid Assistive Technology Capacity Survey (World Health Organization Regional Office for Africa)

ATLAS.ti | The #1 Software for Qualitative Data Analysis (ATLAS.ti)
ATLAS.ti helps you uncover actionable insights with intuitive research tools and best-in-class technology. Try it for free today!

BE2_Cost_Measurement_Guidance_Note_Final.pdf

BE2_Guidance_Note_Generating_Evidence.pdf

BI-COVID-19-Rapid-Assessment-Round2_20200424.pdf

C4DLab – Innovation Hub

CADIMA

Calculating the Educational Impact of COVID-19 (Part II): Using Data from Successive Grades to Estimate Learning Loss | SharEd

Center For Global Development
The Center for Global Development works to reduce global poverty and inequality through rigorous research and active engagement with the policy community to make the world a more prosperous, just, and safe place for us all.

CIES_CostGuidance_finalslides.pdf

Cochrane Reviews | Cochrane Library
The Cochrane Library is a collection of high-quality, independent evidence to inform healthcare decision-making. Six databases are available including the Cochrane Database of Systematic Reviews and a register of controlled trials.

COCI, the OpenCitations Index of Crossref open DOI-to-DOI citations

colandr

colandr
Keywords: _Added-ailr-2024

COMMISSIONREPORT-RECENT1.pdf

Connected Papers | Find and explore academic papers
A unique, visual tool to help researchers and applied scientists find and explore papers relevant to their field of work.

Connecting Learning Spaces: Possibilities for Hybrid Learning

Consensus: AI Search Engine for Research (Consensus: AI Search Engine for Research)
ChatGPT for Research. Consensus is an AI-powered search engine that finds and summarizes scientific research papers. Just ask a question!
Keywords: _Added-ailr-2024

Consensus & GPTs for Academic Research Like Consensus (2024)

Core Final Report_16Dec2016_0.pdf

COVID-19 and girls' education: A tale of two futures
Julia Gillard will join UK Special Envoy for Girls' Education Baroness Sugg and youth from around the world for a dialogue on how COVID-19 is affecting girls' education from around the world

Covidence - Better systematic review management

Creating Localizable Learning Apps

Creative Commons — Attribution 4.0 International — CC BY 4.0

Creative Commons (Home) (Creative Commons)
Open access to knowledge is critical—especially during a global health emergency. The Open COVID Pledge calls on organizations around the world to make their patents and copyrights freely available in the fight against the COVID-19 pandemic. CC’s Response to COVID-19

DeepL Translator
Use the free DeepL Translator to translate your texts with the best machine translation available, powered by DeepL’s world-leading neural network technology. Currently supported languages are English, German, French, Spanish, Portuguese, Italian, Dutch, Polish, Russian, Japanese, and Chinese.

delfi2019/delfi.org · master · Jens Lechtenbörger / publications (GitLab)
Source files for selected publications

Demographic and Health Survey

Developments in Literacy

Devising New Models for School Improvement in Developing Nations: Sierra Leone, a case study

Disability Inclusive Education Toolkit | Education Links
This toolkit provides guidance and resources for integrating disability into the USAID Program Cycle.

DistillerSR | Systematic Review Software | Literature Review Software (DistillerSR)
DistillerSR is the leading systematic review software that automates every stage of your review to produce evidence-based research faster and more accurately.
Keywords: _Added-ailr-2024

dmetar - Companion R Package for the Guide Doing Meta-Analysis in R
Serves as the companion R package for the open-source guide Doing Meta Analysis in R. Aimed at beginners, the package contains complementary functions to facilitate performing meta-analysis using the meta, metafor, netmeta and gemtc packages.
Keywords: _Added-ailr-2024

Document Detail (World Bank)
Remote-learning, Time-Use, and Mental Health of Ecuadorian High-School Studentsduring the COVID-19 Quarantine (English)

E-learning and Pakistan - An Era of Modern Education - University of Leeds
E-learning and Pakistan - An Era of Modern Education-conference_proceeding

Early Years Toolkit
An accessible summary of educational research for early years teaching

ED540960.pdf

EdTechHub (internal) 2339240 | Zotero

Edu TV Kenya (Youtube)

Education Commission (Education Commission)
The Education Commission is a global initiative encouraging progress on Sustainable Development Goal 4 – inclusive and quality education for all. The Commission is creating a pathway for education reform and increased investment by mobilizing strong evidence and analysis.

Education Country Status Report: An analysis for further improving the quality

education-during-covid-19-crisis.pdf

Education in Cambodia | Where We Work | Global Partnership for Education
See education data for Cambodia and learn about GPE programs, grants, results and progress.

Education in Emergencies v3 (1).pdf

Education.pdf

Educational Technology as Systems Approach - WikiEducator

eKitabu

Elicit: Find scientific research papers
Keywords: _Added-ailr-2024

Enabling Education Network

EPPI-Reviewer

EPPI-Reviewer: systematic review software
Keywords: _Added-ailr-2024

Exotel helps Saarthi Education understand their program success with call pickup and completion rates (India)

Exotel Powering Vedantu’s Mission of Making Learning Personalized (India)

Extending and scaling technology-based innovations through research | READ online (OECD iLibrary)
This chapter examines the question of 21st century skills through the prism of a case study on Singapore. Certainly, this case is quite particular in

FAQs -
Frequently Asked Questions: Questions You Have About Inclusive Education But Didn’t Know Whom To Ask Inclusion International is often asked what we mean by “inclusive education”. Here are the most common questions from our members together with our responses. The responses are based on the …

FCDO - GEC
Keywords: auto_merged

file.pdf

Financing education in Malawi: Opportunities for action. Country case study for the Oslo Summit on Education for Development. - Malawi (ReliefWeb)
English Analysis on Malawi about Education; published on 10 Jul 2015 by Govt. Norway

Five Findings from a New Phone Survey in Senegal (Center For Global Development)
Better data can help us have a better response for COVID, so we piloted a mobile phone survey on 1,000+ respondents in Senegal in partnership with the Centre de Recherche pour le Développement Économique et Social. We published the results of the survey yesterday and we are now publishing some of the key findings.

Fixed telephone subscriptions (per 100 people) - Rwanda | Data

Focus Country: Kenya (EdTech Hub)
Kenya Focus country EdTech Hub works in six focus countries (Bangladesh, Ghana, Kenya, Pakistan, Sierra Leone and Tanzania) to conduct research, support governments, and support scale-up of EdTech programmes.   “Female students with teacher on computer” by Ericsson Images is licensed under CC BY-NC-ND 2.0 READ KENYA COUNTRY SCAN Population: 47.6 million Median age: 20 years Internet penetration: 43% Mobile penetration:…

Full article: Educational technology for learners with disabilities in primary school settings in low- and middle-income countries: a systematic literature review

Future Tools - Find The Exact AI Tool For Your Needs
FutureTools Collects & Organizes All The Best AI Tools So YOU Too Can Become Superhuman!

generate.pdf

Ghana Education Service

Ghana Library Authority (2020)

ghana_ict_in_education_policy_august_2015.pdf

Global Monitoring of School Meals During COVID-19 School Closures.
As a result of school closures, 350 million children around the world are missing out on school meals. For many of them, a school meal may be their only nutritious meal during the day. The world needs to find alternative solutions, fast.

Google Meet

Google Translate

google translate - Google Search

Government of Pakistan. Ministry of Federal Education and Professional Training

Government of Pakistan. Ministry of Information Technology & Telecommunication, Government of Pakistan

Government of Pakistan. Ministry of Information Technology & Telecommunication, Government of Pakistan

Government of Sindh. Information Technology Department Government of Sindh

Government of Sindh. Information Technology Department Government of Sindh

Government of the Punjab. Punjab Information Technology Board

Government of the Punjab. Punjab Information Technology Board

Government of the Punjab. School Education Department

Grantable
Keywords: _Added-ailr-2024

GSMA-State-of-Mobile-Internet-Connectivity-Report-2019.pdf

Guidance Note on Qualitative Research final2020.pdf

Haßler et al_2014_School-based professional development in a developing context.pdf

HDR19 Curated list: French resources on introducing technology in the classroom

Home - Ubongo Learning | African Children's Media & Edutainment (Ubongo)
Ubongo is Africa's leading children's edutainment and media company. As a non-profit social enterprise, Ubongo provides millions of families across Africa with fun, localised and multi-platform educational content that helps kids learn, and leverage their learning to change their lives.

How Systems Thinking Applies to Education - Educational Leadership

How to Use ChatGPT for Academic Purposes (Academic Insight Lab)
Exploring the ethical concerns and legitimate uses of ChatGPT in academic settings, including knowledge curation, data analysis, and generating new data points. Best practices for using ChatGPT are also discussed. Join today for free and begin using our AI tools, which are built using the most advan

Humanitarian OpenStreetMap Team | Home

Idara-e-Taleem-o-Aagahi

iHub

ILMA
Innovate.Collaborate.Educate.

Implementation Strategy for the National ICT Policy

Implementing large-scale instructional technology in Kenya: Changing instructional practice and developing accountability in a National Education System | SharEd

Information Technology and Student Achievement: Evidence from a Randomized Experiment in Ecuador

Instant Network Schools Programme, United Nations High Commissioner for Refugees (UNHCR) and the Vodafone Foundation / May 2016 - December 2017 | United Nations Office for Partnerships

International Astronomical Union | IAU

International Centre for Evidence in Disability (LSHTM)

International Review of Research in Open and Distributed Learning (Érudit)
The International Review of Research in Open and Distributed Learning (www.irrodl.org) est une revue numérique à comité de lecture qui diffuse des r…

Introduction to Systems Theory | Wiley (Wiley.com)
Niklas Luhmann ranks as one of the most important sociologists and social theorists of the twentieth century. Through his many books he developed a highly original form of systems theory that has been hugely influential in a wide variety of disciplines. In Introduction to Systems Theory, Luhmann explains the key ideas of general and sociological systems theory and supplies a wealth of examples to illustrate his approach. The book offers a wide range of concepts and theorems that can be applied to politics and the economy, religion and science, art and education, organization and the family. Moreover, Luhmann’s ideas address important contemporary issues in such diverse fields as cognitive science, ecology, and the study of social movements. This book provides all the necessary resources for readers to work through the foundations of systems theory – no other work by Luhmann is as clear and accessible as this. There is also much here that will be of great interest to more advanced scholars and practitioners in sociology and the social sciences.

invest2innovate

Iris.ai - Your Researcher Workspace – Leading AI for your research challenge (Iris.ai - Your Researcher Workspace)
AI for scientific text understanding - literature reviews, research data extraction, post-market surveillance, and other tedious tasks.
Keywords: _Added-ailr-2024

Join this video meeting
Real-time meetings by Google. Using your browser, share your video, desktop and presentations with team members and customers.

JSTOR: Search Results

Keep Children Reading: Monitoring Reading Data During Covid-19

Keep Kenya Learning

Kenya Education Cloud
home

Kenya Education Management Institute

Kenya - Scoping review (Google Docs)
Executive summary A concise summary of the high-level takeaways, to detail: What is already known on the topic What this paper adds What the Implications are for practice and / or policy Introduction [1 page maximum. The majority of the introduction will be standardised text across all six re...

Kenya Vision 2030

Kheda Communication Project

Knowledge Platform

Konnect

KUKUA

Kukua Education

Landscape Review: Education in Conflict and Crisis - How Can Technology Make a Difference? | INEE

Lateral.io: Enhancing Literature Review Speed
Lateral.io is a tool that helps researchers save time and improve efficiency by organizing and analyzing research papers, allowing for faster information retrieval and collaboration.
Keywords: _Added-ailr-2024

Lean Impact: How to Innovate for Radically Greater Social Good | Wiley (Wiley.com)
Despite enormous investments of time and money, are we making a dent on the social and environmental challenges of our time? What if we could exponentially increase our impact? Around the world, a new generation is looking beyond greater profits, for meaningful purpose. But, unlike business, few social interventions have achieved significant impact at scale. Inspired by the modern innovation practices, popularized by bestseller The Lean Startup, that have fueled technology breakthroughs touching every aspect of our lives, Lean Impact turns our attention to a new goal - radically greater social good. Social change is far more complicated than building a new app. It requires more listening, more care, and more stakeholders. To make a lasting difference, solutions must be embraced by beneficiaries, address root causes, and include an engine that can accelerate growth to reach the scale of the need. Lean Impact offers bold ideas to reach audacious goals through customer insight, rapid experimentation and iteration, and a relentless pursuit of impact. Ann Mei Chang brings a unique perspective from across sectors, from her years as a tech executive in Silicon Valley to her most recent experience as the Chief Innovation Officer at USAID. She vividly illustrates the book with real stories from interviews with over 200 organizations across the US and around the world. Whether you are a nonprofit, social enterprise, triple bottom line company, foundation, government agency, philanthropist, impact investor, or simply donate your time and money, Lean Impact is an essential guide to maximizing social impact and scale.

learning-through-play-school.pdf

litbaskets
LITBASKETS — Supporting literature searches for Information Systems researchers.
Keywords: _Added-ailr-2024

LitSonar
Keywords: _Added-ailr-2024

Logic Model Development Guide (W.K. Kellogg Foundation)
Nonprofits today are being pressed to demonstrate the effectiveness of their program activities by initiating and completing outcome-oriented ...

Longhorn eLearning

Low-Tech Personalised Learning to Improve Girls’ Education in Kenya (led by M-Shule)

M-Shule
M-Shule is an SMS knowledge-building platform that helps organizations deliver Learning, Evaluation, Activation, and Data tools across East Africa.

Makani centres – a safe space to learn and make new friends
Aisha and Yasmeen, from diverse backgrounds and speaking different languages, learn to understand each other

Meeting the Data Challenge in Education

Metis

Ministère de l’Économie Numérique et des Télécommunications

Ministère de l’Éducation National

Ministère de l'Enseignement Supérieur, de la Recherche et de l'Innovation - Gouvernement du Sénégal

Ministry of ICT & Innovation

mLab East Africa (World Wide Web Foundation)
Overview Project: mLab East Africa Summary: mLab aims to foster innovation and entrepreneurship within the Kenyan community, with a focus on Web and mobil

Mobile cellular subscriptions (per 100 people) - Rwanda | Data

MOJA (BRCK)
INTERNET FOR EVERYONE Follow Moja: What is Moja? Moja is BRCK’s free public WiFi network. Anyone within range of the signal can connect to the internet for free and access Moja’s stored content to watch shows, listen to music, or read books. With Moja, users pay to get online with their time, attention, or engagement ... read more

Monitoring of continuité pédagogique (Radio Mali) in SIRA project zones

Muktopaath

National-COVID-19-Preparedness-and-Response-Plan_08-04-2020_Final-Version.pdf

National Incubation Center
The National Incubation Center is Pakistan’s largest technology incubation center; the first purpose built creative space in Pakistan buzzing with innovators, mentors, change-makers and passionate leaders. It’s a living example of a successful public-private partnership between the Ministry of IT & Telecom, Ignite – National Technology Fund, Jazz and Teamup. The National Incubation Center in Islamabad is led by two unicorn founders with around decades of combined experience in setting up organizations from scratch and bringing digital revolution in Pakistan.

NETP17.pdf

[No title found] (Saudi Journal of Humanities and Social Sciences)
Throughout the world, the Information and Communications Technology (ICT) is changing the face of education. This paper is a report of a study that was carried out in the months of May and June 2016 on the availability of resources and facilities for ICT integration in the public primary school curriculum in Kitui County in Kenya. The research purpose and objective of the study was: To find out the availability of resources and facilities for ICT integration in the public primary school curriculum in Kitui County. This study was guided by the Technology Acceptance Model (TAM). It was informed by the pragmatic philosophy and the Mixed Method (MM) research approach. Data was collected from 388 public primary schools in Kitui County selected through stratified and simple random sampling methods. A total of 388 head teachers and 776 teachers participated in the study giving a total of 1114 respondents. The research instruments used were questionnaires for teachers, interview schedules for head teachers and observation checklists. The data collected was analyzed qualitatively and quantitatively. The findings revealed that most of the schools were connected to electricity but lacked ICT resources such as desk computers, whiteboards, CD-ROMs and anti-viruses. Laptops were available in some of the schools but were not being used by teachers in direct instruction. They were mainly used in the storage of school records, teacher plans, examination questions and for examination registration exercises. Another finding was lack of internet connectivity in most of the schools that affected ICT integration in the curriculum. The study recommended that the education stakeholders and the government should partner in provision of ICT resources and facilities to facilitate integration of ICT in schools. It is hoped that this study will be useful in education policy making on ICT integration in schools in Kenya and other parts of the world.

NVivo (Lumivero)
NVivo qualitative data analysis software helps to discover richer insights from your qualitative & mixed methods research. Organize, store, and analyze data today!

OER PD - EdTech Hub

Open Learning Exchange – Ghana

OpenAI API Pricing 2024: Understanding GPT-3 Pricing In-Depth
Discover what determines the GPT-3 pricing and how to calculate the approximate cost for your project.

opendoor.col.org

ORKG Ask | Find research you are actually looking for

Pakistan country scan_0614 (Google Docs)
{"zoteroitem":"2405685:FIQDEKCI","zoterobib":"","zenodo":"10.5281/zenodo.3911655","status":"","series":"","number":""}

pakistan1118_insert_lowres_webspreads.pdf

Parsifal - Perform Systematic Literature Reviews (Parsifal)
Parsifal is a tool to support researchers to perform systematic literature reviews. Performing a systematic literature review is a labor-intensive task that requires a huge amount of work from the researcher. Parsifal will help you planning, conducting and reporting the review.

[PDF] Establishing a Safe Container for Learning in Simulation: The Role of the Presimulation Briefing | Semantic Scholar

(PDF) Pedagogic change by Zambian primary school teachers participating in the OERS4Schools professional development programme for one year | Sara Hennessy - Academia.edu

Perplexity

PR122.pdf

Public Documents Profile Viewer

Qdrant - Vector Database
Qdrant is an Open-Source Vector Database and Vector Search Engine written in Rust. It provides fast and scalable vector similarity search service with convenient API.

Read Foundation

Redirecting

Registration for the Online Design Studio for second semester courses (Google Docs)
Please complete the form below to register for the CILT design studio sessions. With the adjusted academic calendar, term 3 (3 Aug - 25 September, with 8 weeks of teaching), will also be delivered remotely. Since the exact date for the return to campus based teaching for everyone is not yet confirmed, designing a blended model for the entire semester (which runs from August until November) will allow maximum flexibility. The challenges faced in the unplanned term 2 emergency remote teaching included developing online course content, engaging with students, developing tutorial-like activities and designing assessments. We are inviting you to join the CILT self-paced course aimed at helping you to modify semester 2 courses for remote conditions. The self paced course provides four rapid design sessions (approximately 3-4 hours per session). Hosted on a Vula site, the course offer practical steps in course design: Session 1: Approaches to remote teaching Session 2: Focus on student learning Session 3: Detailed module design Session 4: Assessment design

Remote Teaching | Centre for Innovation in Learning and Teaching

RER-Accelerated-Learning-and-EdTech.pdf

Research - Edtech Solutions | All Children Reading (All Children Reading: A Grand Challenge for Development)
Explore ACR GCD’s in-depth research on the impact of edtech solutions on improving reading outcomes for children in low-resource contexts.

Research on Open Educational Resources for Development (ROER4D)

Research Rabbit
Keywords: _Added-ailr-2024

Rethinking research partnerships: Evidence and the politics of participation in research partnerships for international development - Fransman - 2019 - Journal of International Development - Wiley Online Library

Revealing Stereotypes: Evidence from Immigrants in Schools
If individuals become aware of their stereotypes, do they change their behavior? We study this question in the context of teachers' bias in grading im...

RevMan
Keywords: _Added-ailr-2024

Right To Education: Pakistan
Right To Education Pakistan (RTE Pakistan) is an organization dedicated to making sure that the state provide free and compulsory education to all children in Pakistan.

RobotAnalyst (National Centre for Text Mining — NaCTEM)
META-NET Project.

RobotReviewer (RobotReviewer)
Keywords: _Added-ailr-2024

Round-1-Report.pdf

Safaricom

SautiUg-EducationWeb.pdf

Scanlitt
Keywords: _Added-ailr-2024

Scholarcy (Scholarcy | The long-form article summariser)
Scholarcy™ is an online summarizing tool that generates and converts long articles into summary flashcards. Sign up free & start summarizing

Scholarcy (Online Summarizing Tool | Flashcard Generator & Summarizer) (Scholarcy | The long-form article summariser)
Scholarcy™ is an online summarizing tool that generates and converts long articles into summary flashcards. Sign up free & start summarizing

Schools, pupils and their characteristics, Academic Year 2019/20
This release contains the latest statistics on school and pupil numbers and their characteristics, including: age gender free school meals (FSM) eligibility English as an additional language ethnicity school characteristics class sizes The publication combines information from the school census, school level annual school census, general hospital school census and alternative provision census.

ScienceDirect Snapshot

SciPub+ | Revolutionize Your Academic Writing
Empowering Researchers with AI-Driven Writing Tools

scite.ai (scite.ai)
Smart Citations for Amoya Rolle

Scite.ai (AI for Research) (scite.ai)
Ask a question, get an answer backed by real research. Scite is trusted by leading universities, publishers, and corporations across the world.

Secondary Education Development Program - SEDP

Semantic Scholar | AI-Powered Research Tool
Semantic Scholar uses groundbreaking AI and engineering to understand the semantics of scientific literature to help Scholars discover relevant research.
Keywords: _Added-ailr-2024

SESRA

Sierra Leone: education country status report; an analysis for further improving the quality, equity and efficiency of the education system in Sierra Leone; 2013

Silverleaf Academy

Simplifying license attribution for OER with emacs-reveal (OER World Map)
Open Educational Resources (OER) come with different license terms that require different forms of attribution. Properly attributing OER with licensing information has previously been identified as one of the most time-consuming factors of OER projects. As shown in this paper, the semantic annotatio

Sisimpur: Homepage (Sisimpur)
Explore games, videos, and activities with Halum, Ikri Mikri, Shiku, and Tuktuki!

Skills

Slack | general | EdTech

Slack | Katy Jordan | EdTech

SMS Voices: Technology Solution for Information-Sharing from Remote Populations

Snapshot

SNE_Policy__4.10.2018.pdf

Solutions

srdb.pro
SRDB.PRO is the first enterprise level literature review and data analysis platform designed specifically for the Pharmaceutical industry and healthcare consultancies. A truly comprehensive literature review solution, supports all aspects of the review process, from searches through to report generation. And all from a single software platform. SRDB.PRO enhances productivity, increases accuracy and drives greater profitability by reducing the amount of time needed to manage and produce accurate reviews and secondary evidence. Visit us at www.srdb.pro

SWIFT-Active Screener (Sciome)
SWIFT-Active Screener is a web-based, collaborative systematic review software application. Active Screener was designed to be easy-to-use, incorporating a simple, but powerful, graphical user interface with rich project status updates. What makes Active Screener special, however, is its behind-the-scenes application of state-of-the-art statistical models designed to save screeners time and effort by automatically prioritizing articles […]

T-TEL (Transforming Teacher Education and Learning)

Tanzania Commission for Science and Technology

Tanzania Commission for Universities

Tanzania Education Authority

Tanzania Higher Education

Tanzania Institute of Education

Tarjemly Live (Tarjemly Live)
Tarjmly Live was created from the difficulty which Arab and foreigners face when they come to Turkey for tourism or residence purposes, the difficulty is in differences in languages, and the difficulty of the Turkish language

Teach by Radio – MINISTRY OF EDUCATION, LIBERIA

Technology and Child Development: Evidence from the One Laptop per Child Program | Publications

Technology for Inclusive Education (TFIE) Pilot Report

Teleschool Inauguration 13-04-2020.jpg

TESS-India Academic Review Final 130617_0.pdf

TESS-India (Teacher Education through School-based Support) (Open Learn Create)

TESSA | Teacher Education in Sub-Saharan Africa (TESSA)

The DAISY Consortium Home Page (The DAISY Consortium)
Global Reach DAISY is an international non-profit membership organization working with over 150 partners all around the world to improve access to reading for people with print disabilities Join Us… Shaping the Technology of Tomorrow At DAISY we work closely…Continue reading...

The Effect of Covid-19 on Education in Africa and its Implications for the Use of Technology (ICDE)
The Effect of Covid-19 on Education in Africa and its Implications for the Use of Technology As African countries begin to come to terms with the effect of the Covid-19 pandemic on their education systems, eLearning Africa and the EdTech Hub conducted a survey of over 1600 education and technology

The Global Initiative for Inclusive ICT (Home) (The Global Initiative for Inclusive ICT)

The National Council for Technical Education (NACTE)

The National Education Act, 1978 (UNESCO)

The Risks of Dangerous Dashboards in Basic Education (Center For Global Development)
Many countries’ systems of basic education are in “stall” condition. A recent paper of Beatty et al. (2018) uses information from the Indonesia Family Life Survey, a representative household survey that has been carried out in several waves with the same individuals since 2000 and contains information on whether individuals can answer simple arithmetic questions. Figure 1, showing the relationship between the level of schooling and the probability of answering a typical question correctly, has two shocking results.

THIRD-MEDIUM-TERM-PLAN-2018-2022.pdf

TMIS Sierra Leone

ToffeeTV (ToffeeTV)
The idea of ToffeeTv stems from arduous hours of searching Urdu stories and songs for children. As the search continues the sad realization has set in that

Transforming Teacher Education and Learning

Trends in Digital Personalized Learning
Landscape review | Taking stock of personalized learning solutions in low and middle-income countries

Tunapanda Institute - Bridging Digital Divides (Tunapanda Institute)
Tunapanda is a swahili word meaning 'we are growing'. We are a non-profit social enterprise that runs intensive 3-month technology, design, and business

Turn.io News: Bridge’s mobile interactive quiz platform uses WhatsApp to mitigate learning crisis
Bridge International Academies is using a WhatsApp-based mobile interactive quiz platform to help deliver solutions to children in Nigeria, Liberia, Uganda and Kenya during the current learning crisis brought on by the COVID-19 pandemic.

Turn.io News: Fast tracking low-cost, scalable EdTech solutions with Turn.io’s Chat for Impact Service
Over the past two years, Turn.io’s Chat for Impact platform has played an important role in supporting social impact organisations around the globe as they develop better and more robust education systems.

Turn.io News: Girl Effect chatbot a safe space for young girls
Girl Effect creates virtual and real-world spaces where girls can be inspired, informed, and connected to services, and to others, so they can take action to change their lives. The partnership with Turn.io has evolved over the last four years into the creation of Big Sis, a virtual “big sister” who offers private and trusted advice about sex and relationships.

Turn.io News: NewGlobe continues to refine remote learning solutions in five countries
NewGlobe has delivered remote learning solutions to over 13 400 users in five countries since a few months into the onset of the COVID-19 pandemic and is using feedback from end-users to significantly enhance the project. Among these solutions is a highly impactful series of chat-based interactive quizzes on mobile designed to reach learners where they are in Nigeria, Liberia, Uganda, Kenya and India, and delivered through NewGlobe’s Bridge Academies International.

Tusome – Improving Early Grade Learning in Kenya | RTI

TV-Based-Learning-in-Bangladesh-Is-it-Reaching-Students.pdf

Typeset (AI Chat for scientific PDFs | SciSpace)
Chat with PDF and conduct your literature review faster using SciSpace. Discover 200M+ papers or upload your own PDF, highlight text or ask questions, and extract explanations and summaries.
Keywords: _Added-ailr-2024

UCT Low Tech Remote Teaching Guidelines (Google Docs)
University of Cape Town Low Tech Remote Teaching Principles Teaching and learning remotely during a global pandemic is a challenging task for everyone. Keep it simple for you and your students. CILT will help you move your course online: reach out to us at help@vula.uct.ac.za, use the rem...

UCT Remote Teaching Course Design Checklist 2020 (Google Docs)

UDL: The UDL Guidelines (The UDL Guidelines)

Universal Service Funds & connecting schools to the Internet around the world
maybe there's another way to support this? We need to connect our schools to the Internet. While it may not (yet) be viable to do so in many countries, few education policymakers would question this general aspiration. Of course, questions related to the speed and nature of this connection are ...

Using educational transitions to estimate learning loss due to Covid-19 school closures.pdf

Using video to support in-service teacher professional development: the state of the field, limitations and possibilities: Technology, Pedagogy and Education: Vol 27, No 1

Virtual Class

Virtual University of Pakistan

Virtual University of Pakistan

Washichana Wetu Wafaulu - Education Development Trust Programme

WebPlotDigitizer - Extract data from plots, images, and maps

Welcome - Humanitarian Data Exchange

What-are-countries-that-already-use-remote-learning-doing-and-what-can-we-learn-from-them-EdTechHub.pdf

What is the AppMap - Google Docs

WonderTree

World Development Report 2018: Learning to Realize Education’s Promise (World Bank)
World Development Report 2018: LEARNING to Realize Education’s Promise

Worldreader | Helping Readers Build a Better World

WPS8050.pdf

Wuqu' Kawoq

Zenodo - Research. Shared.

শিক্ষক বাতায়ন

a2i website - a2i

Home - Abwaab

Academic Bridge | Tomorrow's Education Today - Academic Bridge

OER Evaluation Criteria - Affordable Learning Georgia

African Storybook - African Storybook

Continental Education Strategy for Africa (CESA 16-25) - African Union (African Union)

Use of Assistive Technology in Inclusive Education: Making Room for Diverse Learning Needs - Ahmad, Fouzia Khursheed (Transcience)
Technology has great potential in providing to all learners the ability to access the general education curriculum, and with effective integration of assistive technology into the regular classroom, students with special needs can have the provision
Keywords: ⛔ No DOI found

Malawi’s leading provider of prepaid, postpaid mobile, & 4G services. Recharge your prepaid mobile & pay your postpaid bills online. - Airtel (Airtel)

Akili and Me – Akili and Me Official Site - Akili and Me

Mapping gender equality in STEM from school to work - Alam, Andaleeb; Tapia, Ingrid Sanchez
Keywords: ⛔ No DOI found

The Use of Instructional Technology in Private Schools and National Education Policy - Ali, Zulfiqar; Ghani, Fazal; Ali, Arshad
Audio Visual Aids (A.V. Aids) are devices, which are used in teaching to make the learning experience more effective and dynamic. A.V. Aids have made improvements in learning process through involving the sense of hearing and/or sense of sight. The history of the A.V aids can be traced back to the Greek period, however, the technological advancement brought new innovations in the form of computer assisted programs and accessories. In comparison with developed countries, the developing countries including Pakistan experience the lack of modern A.V. Aids as well as the required technical know-how for their effective use. The aim of this paper is to explore the use of A.V. Aids, their type, teachers’ training for their effective use, policy imperatives and role of private public schools in adoption of A.V. Aids in education in private schools in district Peshawar, KP province. To achieve objectives of the study, data was collected from teachers of private schools through close and open ended questionnaire. Information was also collected from books, government’s reports, published research and internet. The findings show that A.V. Aids are used in all private schools in some form. However, there is no system to give formal training to teachers about the proper and effective use of A.V. Aids. The major A.V Aids used in schools are chalk board and white board, while about 60 % schools were found using pictures, maps, models charts and multimedia. The paper gives practicable suggestions to widen the use of A.V. Aids and enhance their effectiveness in education.

Aliim – Smartphone Schools Program - Aliim.org

All Children Reading: A Grand Challenge for Development [Report] - All Children Reading (USAID; World Vision; Australian Aid)
ACR GCD provides an overview and results of 32 innovations piloted from 2012-2014 to improve early grade literacy in developing countries.

All Children Reading: A Grand Challenge for Development [Web Page] - All Children Reading (All Children Reading: A Grand Challenge for Development)
Advancing edtech innovation and research to improve reading outcomes for marginalized children in low-resource contexts. Learn more here.

EduApp4Syria Prize - All Children Reading: A Grand Challenge for Development - All Children Reading

Bangladesh National ICT Household Survey: report and overview of main results 2018-2019 - Alliance for Affordable Internet; A2I Programme

All Trials Registered. All Results Reported - AllTrials (AllTrials)

Amira Learning Home Page - Amira Learning
The only reading solution designed to achieve measurable reading growth and curriculum coherence through the powerful synergy of AI and neuroscience.

Can Low-Tech Solutions Improve Rohingya Teachers' Pedagogical Skills in Cox's Bazar, Bangladesh? - Andra, Nishitha (Refugee Teachers: The Heart of the Global Refugee Response)

Arifu - Arifu

ACLED Conflict Index: Global conflicts double over the past five years - Armed Conflict Location & Event Data (ACLED)
Updated December 2024: The ACLED Conflict Index calculates where conflicts in every country and territory in the world vary according to four indicators – deadliness, danger to civilians, geographic diffusion, and the number of armed groups.

Statistical Data/Dadus Estatistiku - Ars (Ministério da Educação)
EMIS system in Timor-Leste is updating not only the current year’s data, but also the previous years’ data as soon as the errors are found, in order...
Keywords: ⛔ No INSPIRE recid found

Autorité de Régulation des Télécommunications et des Postes - ARTP SENEGAL

ATLAS.ti AI Lab | Accelerating Innovation for Data Analysis - ATLAS.ti
Powered by OpenAI, ATLAS.ti revolutionizes qualitative data analysis — bringing you light-speed insights.

Supporting out-of-school girls and marginalised groups - Australian Council for Educational Research (ACER)
Supporting out-of-school girls and marginalised groups

What is Autism? - Autism Research Institute (Autism Research Institute)
Autism is a developmental disorder that appears within the first three years of life. Learn about symptoms, diagnosis, and treatment.
Keywords: ⛔ No INSPIRE recid found

Aprendo en línea | Ayuda Mineduc - Ayuda Mineduc

Covid-19 au Sénégal: Pour une continuité pédagogique, le ministère de l’Education lance « Apprendre à la maison » - Badiane, Seydou (Socialnetlink, le lien vers l'actu IT africaine et des startups)
En cette période de pandémie, plusieurs pays ont décidé de fermer les établissements scolaires. En conséquence, des millions d’élèves sont...

BUILDING E-TEACHING CAPACITY OF TVET LECTURERS TO CUSHION THE EFFECTS OF COVID-19 AND OTHER FUTURE PANDEMICS ON TERTIARY EDUCATION SYSTEM OF LOW AND MIDDLE INCOME COUNTRIES - Bakare, Jimoh; Oviawe, Jane Itohan; Nwachukwu, Christiana; Anoure, Nonesta Chidiebere; Anayo, Madu Maureen; Maghalu, Favour Amarachi
Keywords: ⛔ No DOI found

Household Income and Expenditure Survey 2016-2017 - Bangladesh Bureau of Statistics (Bangladesh Bureau of Statistics)
Keywords: ___working_potential_duplicate

Go Girls Connect! - The Bantwana Initiative of World Education Inc., - Bantwana World Education Initiative (Bantwana)
Go Girls Connect! is an innovative program leveraging mobile technology to empower girls to advocate for their human rights.

Siyakha Girls Economic Empowerment Initiative - Bantwana World Education Initiative
Bantwana’s Siyakha Girls model is designed to strengthen the economic resilience of vulnerable adolescent girls and young women (AGYW).

Siyakha Girls Pilot - Bantwana - Bantwana World Education Initiative

The centrality of peer interaction in technology-supported personalized learning - Bapna, Akanksha

Remote Learning During the Global School Lockdown: Multi-Country Lessons - Barron Rodriguez, Maria; Cobo, Cristobal; Muñoz-Najar, Alberto; Sánchez Ciarrusta, Iñaki (World Bank Group)
Remote Learning During the Global School Lockdown : Multi-Country Lessons (Vol. 2) : Interactive Document (English)

Remote Learning During the Global School Lockdown: Multi-Country Lessons - Barron Rodriguez, Maria; Cobo, Cristobal; Muñoz-Najar, Alberto; Sánchez Ciarrusta, Iñaki (World Bank Group)
Remote Learning During the Global School Lockdown : Multi-Country Lessons (Vol. 2) : Interactive Document (English)

Teachers’ professional development through integrating ICT in English language education: A case from Pakistan - Bashiruddin, Ayesha
Keywords: ⛔ No DOI found

Accelerating Foundational Literacy and Numeracy Through Focus, Measurement, Support and Accountability - Beehary, Girindre (The World Bank)
Today, nine in ten girls and boys in low-income countries (LICs) cannot read with comprehension by their tenth birthday. The pursuit of secondary education, the pathway to employment for the majority of youth in LICs, is thus severely compromised.

Guide for Handling Potential Reputational Risks to UNICEF From Teaching and Learning Materials: Protocol for reviewers - Belot, Marie Noelle

Parent-Child Information Frictions and Human Capital Investment: Evidence from a Field Experiment - Bergman, Peter

Behind Bangladesh’s Protests: Rising Frustration - Bhattacherjee, Aparupa (The Diplomat)

Big Launcher, Big Phone, Big SMS for seniors - Big Launcher
A fast and simple Android home screen for seniors and people with vision problems.

Acceptable Usage Policy - Bishops Diosecan College (Bishops Diosecan College)

Down Syndrome - Boston Children's Hospital
Keywords: ⛔ No INSPIRE recid found

Wander Lowie - Bot, Kees De; Verspoor, Marjolijn
approach to second language acquisition∗

Korail - BRAC

BRCK - Funding, Financials, Valuation & Investors - BRCK (Crunchbase)
BRCK is an integrated hardware and software company based in Nairobi, Kenya.

EDUCATION - BRCK (BRCK)
Hardware, software and connectivity tools to enable learning BRCK Education turn any classroom into a digital classroom. Reaching thousands of children in over 100 locations across 17 countries, our world-class education technology solutions give access to digital educational tools for better learning. INTERNET OF THINGS (IOT) CONNECTIVITY EDUCATION Kio Kit THE DIGITAL CLASSROOM IN A ... read more

Hardware, software and connectivity tools to enable learning - BRCK (BRCK)
Hardware, software and connectivity tools to enable learning BRCK Education turn any classroom into a digital classroom. Reaching thousands of children in over 100 locations across 17 countries, our world-class education technology solutions give access to digital educational tools for better learning. INTERNET OF THINGS (IOT) CONNECTIVITY EDUCATION Kio Kit THE DIGITAL CLASSROOM IN A ... read more

Safeguarding Girls and Boys: When Chatbots answer their private questions - Brown, Isabelle Amazon; Binder, Gerda (UNICEF)

Mobile Phone Subscribers in Bangladesh February, 2020 | BTRC - BTRC

Towards developing interactive content for enhancing life skills education in Tanzania: Possibilities and pitfalls - Budoya, Christian M.; Kissaka, Mussa M.; Mtebe, Joel S. (Springer International Publishing, 2019)
Feasibility study is the first and important stage in any planning of introducing a new solution for overcoming existing challenges. It saves a lot of resources that could be lost if such solution fails to solve the intended problem. On the other hand, it gives a proper way to go ahead with the plan of introducing the solution. The purpose of this study is to establish necessary and basic requirements as possibilities and pitfalls for deploying cost effective interactive multimedia content for enhancing an ineffective provision life skills education at primary school level in Tanzania. Ten primary schools were randomly selected and surveyed from which 65 teachers and 407 pupils participated in the study. Questionnaires, interviews, and documentary reviews were used as data collection tools. It was found that the Internet penetration is 45% of the population with 82.6% of Internet users are smartphones users. Number of computers and tablets at schools are still limited to 1:1036 computer pupils ratio, 96% of pupils had access of computers and smartphones from parents. Moreover, 77% of teachers used conventional and lecturing style in teaching, 100% of life skills content was static found in inadequate textbooks. Based on these results, deployment of self-learning enabled interactive multimedia content is possible and will bring positive impact if it will be developed to operate in ICT devices available in both primary schools and pupils’ parents as well. This study informs the proper way of introducing cost-effective interactive multimedia content at primary school level in Tanzania.
Keywords: Interactive multimedia content; Life skills education; Possibilities and pitfalls

Instructional design enabled Agile Method using ADDIE Model and Feature Driven Development method - Budoya, Christian; Kissaka, Mussa; Mtebe, Joel (The International Journal of Education and Development using Information and Communication Technology, 2019)
Software developers nowadays are adopting agile methods to overcome challenges faced by traditional methods in developing software. However, agile methods lack instructional design to take care of learning needs required in designing software for supporting teaching and learning. This study aimed at designing an integrated model using Feature Driven Development Process (FDDP) and Analysis, Design, Development, Implementation, and Evaluation (ADDIE) model to accommodate learning needs at design stage. Participatory action research method and four design strategies including decompositional, compositional, template based, and incremental and evolutionary strategies were used in designing the integrated ADDIE-FDDP Model. A case study of designing Interactive Multimedia Content for Life Skills Education (IMCLSE) was used to test the model, especially its analysis and design phases. A questionnaire was adapted to evaluate the IMCLSE design involving 10 software developers and 65 teachers who teach life skills subjects in 10 primary schools. The results show that software developers and teachers agreed that the integrated FDDP-ADDIE Model was effective in guiding the design process of software that support teaching and learning. Therefore, the integrated FDDP-ADDIE Model can be adopted and used for developing effective and quality learning software.
Keywords: ⛔ No DOI found

Leh wi Lan - Sierra Leone Secondary Education Improvement programme - Cambridge Education

Leh wi Lan - Sierra Leone Secondary Education Improvement programme - Camb-Ed - Cambridge Education

Technology Supported Learning in Tanzania - Camfed

Uso de las TIC ́s en el tránsito de lo presencial a lo virtual durante la pandemia del COVID-19: El caso de la Escuela Normal Rural de Zacatecas - Castillo, Alejandro Guadalupe Rincón; Peña, Héctor Hugo Zepeda; Coutiño, Luis Antonio Domínguez
Keywords: ⛔ No DOI found

CBM Digital Accessibility Toolkit - CBM (2018)

CBM Policy on Accessibility - CBM (2018)

Education de Base (EDB) Program - Center for Education Innovations

Ghana Reads - Center for Education Innovations
Seeking to improve literacy among elementary level children from low-income families, the Ghana Reads program provides teacher "coaches" that help teachers d...

Senegal Education de Base (EDB) Project - Center for Education Innovations (FHI 360)
The Education de Base (EDB) project improves the quality and governance of the middle school education system in Senegal, working at the national (policy and systems), regional and school levels.

The World Factbook - Central Intelligence Agency

Making EdTech Systematically Reach the Last Mile - Central Square Foundation
When technology first began to be used in schools, it was limited to setting up computer labs to equip students with basic computer skills. Since then, EdTech interventions have evolved from their earlier, more limited avatar. In their current version, they take the form of advanced solutions that are designed to support and enhance teacher-led learning and improve student outcomes.

Education and Learning Materials - CGA Technologies

Sierra Leone Teacher Management Information System (TMIS) - CGA Technologies (CGA Technologies)

Scaling Up Early Grade Reading in Senegal - Chemonics International
Over the last two decades, Senegal has made notable progress toward increasing the number of children who enroll in and complete primary school. Now, the government is pursuing nationwide reform to ensure the quality of classroom instruction is high and inspire families and communities to become involved in helping children learn. USAID/Lecture Pour Tous is […]

Bangladesh: flexible learning for slum dwelling children - Children on the Edge (Children on the Edge)
Together with our partner MUKTI, we support nine Community Schools specifically set up to help working children in the Cox’s Bazar beach area.

Enhancing the EdTech Ecosystem in a British Columbia School District - Chisholm, Suzanne J
Technology has brought significant opportunities to education, but they are largely being lost. In many cases, spending on educational technology (EdTech) has not resulted in improved student outcomes. This Organizational Improvement Plan (OIP) addresses the problem of practice (PoP) of a lack of a framework and supports for K-12 teachers to effectively utilize EdTech in classrooms in the Canadian province of British Columbia (BC). Using a BC school district as a case study, I propose strategies for how leaders can craft and implement a change plan to enhance an EdTech ecosystem that best supports teachers and learners. Establishing a framework for effective use of EdTech in schools is complex and multifaceted. Investments in technology must support best pedagogical practices, and leaders must create conditions that boost teachers’ Technological, Pedagogical and Content Knowledge (TPACK; Mishra & Koehler, 2006). Leaders must adapt to shifting power dynamics in which teachers have new roles as emergent leaders. Optimizing the impact of EdTech in education requires a confluence of three key factors: technology, pedagogy, and excellent leadership. The change process must be iterative, ongoing, stakeholder-driven, and system-wide. This OIP blends Appreciative Inquiry (Cooperrider, 1986) principles with servant leadership (Greenleaf, 1970) and incorporates the district’s existing approaches into a hybrid transformational leadership model. I explore a three-pronged solution of EdTech capacity building for teachers, an EdTech vetting system, and a supportive leadership framework. This aims to raise TPACK, optimize EdTech usage, support wise pedagogy, and improve student outcomes.
Keywords: ⛔ No DOI found

E-Learning in Secondary Schools - Christianity Social Services Commission

CIA World Factbook - CIA

Free Online Textbooks, Flashcards, Adaptive Practice, Real World Examples, Simulations - CK-12 Foundation
CK-12 Foundation provides a library of free online textbooks, videos, exercises, flashcards, and real world applications for over 5000 concepts from arithmetic to history

Georgia, CK-12 and UNICEF Collaboration | - CK-12 Foundation

Neurodivergent: What It Is, Symptoms & Types - Cleveland Clinic
Keywords: ⛔ No INSPIRE recid found

Elimika LMS – Unlimited Learning Experiences - Cloud, Elimika is Powered by Kenya Education

Accessibilities | COL - CoL

Ghana | COL - Commonwealth of Learning

Home | COL - Commonwealth of Learning

Introduction to Technology-Enabled Learning | MOOCs For Development - Commonwealth of Learning

OAsis Home - Commonwealth of Learning

OER for Open Schooling (OER4OS) | COL - Commonwealth of Learning

Open/Innovative Schooling | COL - Commonwealth of Learning

A Short Case Study of the Impacts of the OLPC Project around the World - Coomar, Sonika; Ryzhov, Ilia
The ambitious One Laptop per Child (OLPC) Program was launched in 2005 and has distributed over 2 million rugged, low power connected laptops to some of the poorest children in the world. The chairman and founder, Nicholas Negroponte, is pioneering an experiment with the OLPC project which could fundamentally alter the dynamics of education in the developing world by bringing literacy, learning and connectivity to the estimated 100 million children who currently do not receive education at a first grade level. In this paper we performed a case study using existing literature where we looked into the situation in six countries. In three of these countries the OLPC project was considered successful and in the other three countries the project did not necessarily live up to the expectations. We explored the factors which lead to the success of the OLPC project in these countries and then we looked into the factors that lead to the inadequate results in some of the other countries.
Keywords: ⛔ No DOI found

Malawi GDP - Gross Domestic Product 2021 - countryeconomy.com (countryeconomy.com)

Key Vote Expected on Brazil’s Artificial Intelligence Legal Framework - COVINGTON
Tomorrow, the Federal Senate of the Brazilian National Congress may have its first vote on the count ...

Report Completed and Submitted - Cowan, Emma
Keywords: ⛔ No DOI found

CC Search - Creative Commons (CC Search)
Empowering the world to share through 6 simple licenses + a global community of advocates for open.

Creative Commons — Attribution 4.0 International — CC BY 4.0 - Creative Commons

Creative Commons — Attribution-ShareAlike 4.0 International — CC BY-SA 4.0 - Creative Commons

When we share, everyone wins - Creative Commons (Creative Commons)
Open Access matters—especially during a global health emergency. The race to find a vaccine for COVID-19 exemplifies why rapid and unrestricted access to scientific research and educational materials is so vital. CC’s Response to COVID-19

"Making visible" inequity: Remote learning with technology during Covid-19 - Crompton, Helen; Jordan, Katy; Wilson, Samuel; Nicolai, Susan (NORRAG)
Keywords: ⛔ No DOI found

Crisis response can and should include education — Curious Learning - Curious Learning

Curious Learning - Curious Learning

Curious Learning, Global Digital Library and Chimple Apps - Languages with IDs - Spec Sheet - Google Sheets - Curious Learning

Literacy League — Curious Learning - Curious Learning

Timeline - Curious Learning

Tools for your toolbox: Collecting data for cost-effectiveness with the Brookings Childhood Cost Calculator - D'Rozario, Jonny; Mitchell, Joel

Social support networks, instant messaging, and gender equity in refugee education: Information, Communication & Society: Vol 22, No 6 - Dahya, N; Dryden-Peterson, S
This paper addresses the role of instant messaging chat groups to support teacher training and gender equity initiatives in Kenyan refugee camps. Our findings are based on survey data with refugee teachers in Dadaab and Kakuma refugee camps (n = 203), group interviews with refugee teachers in Kakuma (n = 21), and interviews with international instructors of teacher training programs in Nairobi, Toronto, and Vancouver (n = 14). In our analysis, we apply amplification theory, feminist science and technology studies paradigms, and considerations of transnational approaches to understand the use of instant messaging among refugee teacher communities. Our framework explores how social and cultural norms are amplified through transnational text and instant messaging related to teacher training and in support of gender equity. Peer-to-peer group chats draw on transnational learning opportunities and expand these engagements through group chats between men and women refugee teachers across camps as well as through community engagement about gender equity initiatives in education. International instructors identify both value and hesitation in navigating the quantity and content of these communications, such as learning more about refugee teachers’ daily lives in the camps and concern about following and managing the amount of communication that can ensue over chat groups. Our work has practical implications for transnational teacher training programs in refugee camps, illuminates how mobile technology and chat groups allow women and men in the community to engage and support girls’ education, and questions how text messaging affects the lived and day-to-day experiences of women refugee teachers.
Keywords: Google Scholar/ "refugee education" ICT; RER theme_supporting educators

Integrating digital personalised learning into pre-primary classroom practice: a teacher-researcher multiple-case study partnership in Kenya - Daltry, Rebecca; Major, Louis; Otieno, Mary; Otieno, Kevin; Jordan, Katy; Moustafa, Nariman
Keywords: ⛔ No DOI found

Define and Frame Your Design Challenge by Creating Your Point Of View and Ask “How Might We” - Dam, Rikke Friis; Siang, Teo Yu (The Interaction Design Foundation)
Defining your design challenge is probably one of the most important steps in the Design Thinking process, as it sets the tone and guides all of the activities that follow. In the Define mode, you sho...

Home - DataWinners (DataWinners)

Deaf Schools and Training Centers in Pakistan - Deaf Reach (Deaf Reach Schools, Training Centers and Colleges in Pakistan)
Deaf Reach is the only branch network of schools and training centers in Pakistan.

Teacher education through school-based support in India (TESS-India): Business Case - Department for International Development (DFID)

A case for mother tongue education? - Desai, Zubeida Khatoom
Keywords: ⛔ No DOI found

Scaling AI to map every school on the planet - Development seed

Principles for Digital Development - Digital Principles

About DIKSHA - DIKSHA

Total Cost of Ownership Model: Use the Total Cost of Ownership Model to budget for your mobile solution - Dimagi Inc (2024)

Sierra Leone Learning Passport - Directorate of Science, Technology and Innovation (Directorate of Science, Technology & Innovation, Government of Sierra Leone)
Sierra Leone Learning Passport   About The Learning Platform also provides more flexible schedules which translates to individualized schedules ensuring that parents/guardians take a more active role in the education of their children/wards. Findings have indicated that critical contributions from the family improve the children’s […]

Giga - DSTI - Directorate of Science, Technology & Innovation (Directorate of Science, Technology & Innovation, Government of Sierra Leone)

Sierra Leone Learning Passport - Directorate of Science, Technology & Innovation (Directorate of Science, Technology & Innovation, Government of Sierra Leone)
Sierra Leone Learning Passport “The first stair to failure is ignorance. Keep learning by leaning on the lap of information and you’ll take the lead!” ― Israelmore Ayivor. Sierra Leone Learning Passport “The first stair to failure is ignorance. Keep learning by leaning on the […]

Assistive Technology for Special Education Students - Disability Rights Washington (Disability Rights Washington)
This publication provides a definition of assistive technology, a brief overview of basic special education requirements related to assistive technology
Keywords: ⛔ No INSPIRE recid found

The Systemic Approach: what is it all about? - Donnadieu, Gérard; Durand, Daniel; Neel, Danièle; Nunez, Emmanuel; Saint-Paul, Lionel
Keywords: ⛔ No DOI found

Integrated GIS Portal - DSTI

E-School Cambodia - e-School Cambodia

EGC-ISSER-Northwestern Ghana Panel Survey - ECG; ISSER (Yale Economic Growth Center)
The EGC-ISSER Socioeconomic Panel Survey is a collaboration between the Economic Growth Center (EGC) at Yale University, the Global Poverty Research Lab at Northwestern University and the Institute of Statistical, Social, and Economic Research (ISSER) at the University of Ghana, Legon. The survey is principally funded and designed by the EGC, Northwestern and ISSER, and carried out and supervised by ISSER.

ECONTENT - econtent.edu.mn

Produits - ED4Free

Aprender a Ler (Learn to Read) - EdTech Center @ World Education (EdTech Center @ World Education)
From 2012-2016, World Education, Inc. implemented the USAID|Aprender a Ler (Learn to Read) program in the northern provinces of Nampula and Zambézia in Mozambique. With the goal of improving early grade reading outcomes for students in grades 1-3, WEI used technology via radios and smartphones as a critical companion to training, coaching, and overall school-community support …

EdTech Hub Rapid Scans - EdTech Hub

Education system management / EMIS / education data – EdTechTools - EdTech Hub

The Impact of GIS-Supported Teacher Allocation in Sierra Leone - EdTech Hub (EdTech Hub)
This systemic mixed-methods study will build evidence on the most feasible approach to GIS-supported teacher allocation in Sierra Leone and assess the impact of this approach on teacher retention and attendance. Discover more...

Using laptops to distribute video sign language lessons to deaf children in Pakistan - EdTech Hub
We tested different EdTech interventions to find out which ones would be most suitable for providing distance learning for deaf children.

EdTech Tulna Evaluation Centre - EdTech Tulna

Educate! | Preparing youth in Africa with the skills to succeed in today’s economy. - Educate! (Educate! | Preparing youth in Africa with the skills to succeed in today’s economy.)
Educate! prepares youth in Africa with the skills to succeed in today’s economy. We tackle youth unemployment by partnering with schools and governments to reform what schools teach and how they teach it, so that students in Africa have the skills to start businesses, get jobs, and drive development

Impact Evaluation Results - Educate!

Impact Evaluation Results - Educate!

Monitoring & Evaluation Approach — Educate! | Preparing youth in Africa with the skills to succeed in today’s economy. - Educate!

Out-of-School Youth Solutions — Educate! | Preparing youth in Africa with the skills to succeed in today’s economy. - Educate!

Basa Pilipinas | EDC - Education Development Center

Abracadabra (ABRA) re-grant - Education Endowment Foundation
Project: Abracadabra (ABRA) - re-grant, Testing an online and a paper based version of a balanced approach to reading.

Dashboard Summary - Education Innovation Challenge

Education Alive - Education Media Unit

Sierra Leone - Education Partnerships Group (Education Partnerships Group)
After a number of years of political instability, Cote d’Ivoire now aims to achieve emerging economy status by 2020.

Innovative Education Workforce Analysis for More Equitable Education: Sierra Leone - Education Workforce Initiative (the Education Commission; Fab Inc.; UK aid; Government of Sierra Leone)

Acceptable Use Policies for the Internet - Education World

Eduq+ – Movva - Eduq+

EduwebTV adalah TV Pendidikan - Eduweb

Models, Theories, and Frameworks: Contributions to Understanding Special Education Technology - Edyburn, Dave L
Keywords: ⛔ No DOI found

Video Catalogue – EENET - EENET

Data Visualization - EGER: Evidence for Gender and Education Resource - EGER

eKitabu - eKitabu (All Children Reading: A Grand Challenge for Development)
Studio KSL helps the deaf community and local content creators in Kenya integrate sign language videos into literacy content.

eLimu - eLimu

Launch of Scopus AI to Help Researchers Navigate the World of Research - Elsevier (www.elsevier.com)
Developed and tested with the research community, Scopus AI combines the world’s largest database of curated scientific literature with responsible AI

Scopus AI: Trusted content. Powered by responsible AI. - Elsevier Products (www.elsevier.com)
Scopus AI combines generative artificial intelligence with Scopus’ trusted content and data to help researchers accelerate their research.

Home - Eneza Education (Eneza Education)

https://enezaeducation.com/ - Eneza Education (Eneza Education)
Eneza Education is an ed-tech company that provides curriculum aligned revision material in all subjects for primary and secondary learners on any device. Our virtual tutor provides access to curriculum-aligned ... Read More

enuma - Enuma

Enuma - Enuma
The Best Learning Solution for Children Around the World

Global Learning XPRIZE Field Test Data Report: Kitkit School - Enuma, Inc.

Automation tools in EPPI-Reviewer - EPPI Reviewer
Keywords: _Added-ailr-2024

What is GIS? | Geographic Information System Mapping Technology - ESRI
A geographic information system (GIS) is a system that creates, manages, analyzes & maps all types of data. GIS connects data to a map, integrating location data with all types of descriptive information.

Preparation of teachers for inclusive education in Lebanon - European Agency for Special Needs and Inclusive Education

Disability inclusion - European Civil Protection and Humanitarian Aid Operations (DG ECHO) (European Commission)
People with disabilities include those who have long-term physical, mental, intellectual or sensory impairments which may hinder their full and effective participation in society.

Madagascar - European Commission - European Civil Protection and Humanitarian Aid Operations (DG ECHO) (European Commission)
Madagascar is exposed to various major climate shocks, including, cyclones, floods and long periods of drought coupled with inflation. The humanitarian situation remains fragile because of the El Niño, natural hazards and economic factors.

Multilingualism - European Parliament (Multilingualism)
The European Parliament has 24 official languages, all of them used on a daily basis. Find out how it all works.

Studies of COVID-19 and Education in LMICs - Evans, David; Acosta, Amina (Google Docs)
Sheet1 Authors,Title,Country,Level,Outcome,Region,Date,Product,Provenance,In twitter thread Angrist N, Bergman P, Brewster C, Matsheng M,Stemming Learning Loss During the Pandemic: A Rapid Randomized Trial of a Low-Tech In...

What is the impact of #COVID19 on children and youth’s access to learning opportunities and on their actual learning in low- and middle-income countries? - Evans, David; Acosta, Amina

Adolescent Girls' Education in Crisis Initiative (AGENCI) - Evidence for Gender and Education Resource (EGER)

Full article: A Digital Journey to Social Change - Fahed, Andrea

FCDO - GEC - FCDO

Digital education - Federal Ministry of Education, Science and Research, Republic of Austria

Feynman AI - Feynman AI
Feynman - An AI assistant to make reading, writing and understanding academic literature easier.

Flickr: Creative Commons - Flickr

Digital Youth in Timor-Leste - Frankie, Love; Wilson, Mike; Sloman, Annie; Fernandes, Zevonia Vieira
Keywords: ⛔ No DOI found; ⛔ No INSPIRE recid found

Redistribution or recognition? A Political-Philosophical Exchange? - Fraser, Nancy; Honneth, Axel (Verso)

Free Software Foundation — working together for free software - Free Software Foundation

A Synchronic Approach to Kinyarwanda Variation Among its Native Speakers - Gabriel, Bazimaziki (International Journal of Linguistics, Literature and Culture)
Keywords: ⛔ No DOI found

Formative and Summative Assessment in the Classroom - Garrison, Catherine; Ehringhaus, Michael (National Middle School Assciation)

Automating Early Grade Reading Assessments (EGRA) in African Languages Using Voice-Recognition AI - Gates Foundation
Cally Ardington of the University of Cape Town in South Africa will develop an AI-powered voice-recognition model that performs Early Grade Reading Assessments (EGRA) in low- and middle-income countries (LMICs). Seventy percent of children in LMICs do not learn to read in any language, which severely affects their overall education and future prospects. Reading assessments, such as EGRA, test children on letter-sound knowledge, word reading, reading connected text, and answering questions on that text. They are critical for supporting reading programs but are currently expensive and time-consuming because they are administered one-on-one. They will perform a pilot study to determine whether a new open-source voice recognition program developed by Facebook (wav2vec), which is especially useful for languages with little training data, can automatically evaluate speech production and assess children's early reading abilities in African languages. They will validate EGRA-AI by adding it to an existing 120-school field trial using standard EGRA.

GDL Radio - GDL Radio (GDL Radio)
GDL Radio This Global Digital Library(GDL) radio collection is provided by USAID. The GDL is part of the Global Book Alliance - bringing books to every child in the world by 2030 Radio materials to be used in the classroom or as a podcast on your smarthpone.

GeoGebra | Free Math Apps - used by over 100 Million Students & Teachers Worldwide - GeoGebra (GeoGebra)
Get our free online math tools for graphing, geometry, 3D, and more!

Worldreader Tablets Have Revamped Reading in Libraries. - Ghana Library Authority (2020)

Kyrgyzstan - Giga

learningequality/sushi-chef-ubongokids - GitHub (GitHub)
Contribute to learningequality/sushi-chef-ubongokids development by creating an account on GitHub.

open-learning-exchange/planet - GitHub (GitHub)
🌍 Planet Learning - Angular application. Contribute to open-learning-exchange/planet development by creating an account on GitHub.

XPRIZE/GLEXP-Team-onebillion - GitHub (GitHub)
onecourse: one app that delivers reading, writing and numeracy. Built by non-profit onebillion. - XPRIZE/GLEXP-Team-onebillion

Global Book Alliance - Global Book Alliance (Global Book Alliance)

Human Development Indices - Global Data Lab

About – Global Digital Library - Global Digital Library

Home - Global Digital Library - - Global Digital Library

Data Must Speak about Positive Deviance Approaches to Learning - Global Partnership for Education (GPEKIX)
Keywords: ⛔ No INSPIRE recid found

Senegal - Global Partnership for Education

Sierra Leone: The power of great teaching in times of crisis | Stories of change - Global Partnership for Education
The Ebola crisis that plagued Sierra Leone in 2014-2016 had an unexpected positive consequence: giving learners access to the country’s best teachers through an innovative radio educational program. This experience served the country well when the COVID-19 pandemic hit.

gnu.org - GNU

A COVID-19 intervention: Using digital escape rooms to provide professional development to alternative certification educators - Gómez, Miguel (Journal of Technology and Teacher Education)

Google Image best practices - Search Console Help - Google

Google Images - Google

Mobile-Friendly Test – Google Search Console - Google

Read Along by Google: A fun reading app - Apps on Google Play - Google
Read Along is a free reading app for Android that helps children have fun while they learn to read. Read Along has an in-app reading buddy that listens to your young learner read aloud, offers assistance when they struggle and rewards them with stars when they do well – guiding them along as they progress. It works best for children who already have some basic knowledge of the alphabet. After the initial download, the app works securely offline. Inspire a love of reading in young learners • Fun game-like experience: Keep young minds engaged with hundreds of stories and word games available in nine languages, including English and Spanish. Build confidence reading out loud with instant rewards of stars and badges • Independent learning: Encourage all young learners to learn at their own pace and track their individual progress. Learners have unique profiles, and each advances on their own reading journey with recommended stories based on their reading level. If needed, they can tap on any word to hear it pronounced Foster learning with confidence • Zero cost with no ads or upsells: Keep them focused on what’s important – reading – and relax knowing there are no in-app purchases • No Wi-Fi or data required: Once downloaded, provide a rich learning experience while relieving worries about unsupervised access to the Internet • Private and secure: No name, age, specific location, contact, email address or phone number is required to use Read Along. Additionally, voice data is analyzed in real time on the device, but not stored or sent to Google servers Languages available: With Read Along, children can read a variety of fun and engaging stories in different languages including: • English • Spanish (Español) • Portuguese (Português) • Hindi (हिंदी) • Bangla (বাংলা) • Urdu (اردو) • Telugu (తెలుగు) • Marathi (मराठी) • Tamil (தமிழ்) With Read Along, children can practice, gain confidence, and grow a lifelong love for reading.

Agile delivery - How to work in an agile way: Principles, tools and governance. - Gov.UK (UK Government)
How to work in an agile way: principles, tools and governance.
Keywords: ⛔ No INSPIRE recid found

Agile delivery - Service Manual - GOV.UK - GOV.UK (UK Government)
How to work in an agile way: principles, tools and governance.

How the alpha phase works - GOV.UK (GOV.UK)
Running a successful alpha phase, building and testing prototypes, and deciding whether to move on to beta.

How the beta phase works - GOV.UK (GOV.UK)
What to do during the beta phase, launching your service in private and public beta and deciding to move on to live.

How the discovery phase works - GOV.UK (GOV.UK)
What to do in discovery, how long it takes, how you know it's finished and deciding when to move on.

How the live phase works - GOV.UK (GOV.UK)
Checking you're ready to go live, keeping your team together and what to do after you go live.

Retiring your service - GOV.UK (GOV.UK)
When to retire a service, considering user needs, telling your users and what to do after the service is retired.

National Numeracy Programme | Malawi - Government of Malawi

Ministry of Federal Education and Professional Training - Government of Pakistan

New Guidelines for the INGOs to work with NDMA / PDMAs in COVID 19 Crises - Government of Pakistan. Ministry of Interior and Narcotics Control

Taleem Ghar: An initiative by Government of the Punjab - Government of the Punjab

Political system - Government of the Socialist Republic of Vietnam
Political system

Prêmio Escola Nota 10 - Government of the State of Ceará

Political System - Government of Timor-Leste

Program of the IX Constitutional Government - Government of Timor-Leste

Timor-Leste's Roadmap for Implemention of the 2030 Agenda and the SDGs - Government of Timor-Leste

GSMA Intelligence - GSMA

Mobile Internet Connectivity 2019: Sub-Saharan Africa Factsheet - GSMA

Informal tools in formal context: Adoption of web 2.0 technologies among geography student teachers in Ghana - Gyamfi, Stephen Adu (International Journal of Education and Development using Information and Communication Technology, 2017)
Despite the popularity of Web 2.0 technologies and their educational benefits in the 21st century classroom environment, their use for teaching and learning purposes is still very limited. This study extended the technology acceptance model (TAM) to empirically examine factors that determine Ghanaian geography student teachers' acceptance of Web 2.0 technologies for pedagogical purpose. A self-reported questionnaire administered to 300 student teachers in two universities in Ghana out of which 254 responded. The results from the stepwise multiple regression analysis showed that technological complexity, perceived usefulness and attitude towards use had a significant direct effect on intention to use Web 2.0 technologies. However, social influence which is an exogenous factor had the strongest influence on the student teachers' intention to use the Web 2.0 technologies than the two key original TAM constructs. Contrary to the original technology acceptance model, statistically, perceived ease of use had no significant influence on perceived usefulness. The findings are intended to provide insights to policy makers about how to design preservice teacher education programmes that address the demands of teaching and learning with Web 2.0 technologies in Ghana in particular and developing world context in general.
Keywords: Computers; Education; Learning; Social networks; Student teachers; Teaching; Wikis; ⛔ No DOI found

Pre-service teachers' attitude towards information and communication technology usage: A Ghanaian survey - Gyamfi, Stephen Adu (International Journal of Education and Development using Information and Communication Technology, 2017)
This study employed the Technology Acceptance Model (TAM) to empirically investigate factors that influence Ghanaian pre-service teachers' attitudes towards Information and Communication Technology (ICT) usage. To achieve this aim, the study extended the TAM framework by adding leadership support and job relevance as exogenous variables. Data were randomly collected from 380 pre-service teachers studying a 3-year Diploma in Education programme in Ghana. Based on a multiple stepwise regression analysis, the findings suggested the following: (1) leadership support significantly influenced perceived ease of use; (2) job relevance significantly influenced perceived usefulness; (3) perceived usefulness significantly influenced attitude towards use; (4) perceived ease of use significantly influenced attitude towards use (5) the TAM is significant for pre-service teacher education context except the relationship between perceived ease of use and perceived usefulness. The study contributed to the literature by validating the TAM in the pre-service teacher education context in Ghana. It also provided several implications for the research and practice of ICT adoption in the developing world context.
Keywords: Attitudes; Computers; Education; Educational technology; Student teachers; Studies; Teaching; ⛔ No DOI found

Developing collaborations and technology for evidence synthesis - Haddaway, Martin Westgate & Neal (Evidence Synthesis Hackathon)
An event series to develop open software for evidence synthesis
Keywords: _Added-ailr-2024

Participatory design of DIY digital assistive technology in Western Kenya | Proceedings of the Second African Conference for Human Computer Interaction: Thriving Communities - Hamidi, Foad; Mbullo, Patrick; Hynie, Michaela; McGrath, Susan; Baljko, Melanie

GENDER, POWER AND PROGRESS - Harper, Caroline; Marcus, Rachel; George, Rachel; D’Angelo, Sophia; Samman, Emma
Keywords: ⛔ No DOI found

Responsible Use Policy: A Guide for Schools - HiddenApp

HJRS | HEC Journal Recognition System - Higher Education Council
HEC Journal Recognition System is the collection of authentic research journals ranked in scheduled categories on the bases of different ranking parameters. It is based on a propriety algorithm designed with the objective of promoting quality in research across various disciplines. HJRS allows the view of a ranked position in a journal as global, in subject area and subcategories.

UNESCO Institute for Statistics - Hiraga, Sulekha Patel Masako; Wang, Lianqin; Drew, Doug; Lynd, Doug
Keywords: ⛔ No DOI found

Managing the Paradox of PublicPrivate University Funding: Bangladesh Context - Hossain, M; Hoque, M

Curated Tools for Teacher Continuous Professional Development - Hub, EdTech (EdTech Hub)
EdTech Hub has created curated lists of teacher professional development (TPD) tools along with evidenced-based advice on how to effectively use them. Because, of course, it’s not only which tool you choose, but how you use it that will determine whether it will lead to better teaching and learning.

Explore EdData Tools - Hub, EdTech (EdTech Hub)
Crowdsourcing Data Technologies for Education in Emergencies

Children of Laos - Humaniam (Humanium)
Major problems such as poverty, lack of hygiene and medical supplies as well as discrimination affect the life of children in Laos.
Keywords: ⛔ No INSPIRE recid found

Humanitarian Data Exchange - Humanitarian Data Exchange (OCHA Services: Humanitarian Data Exchange)

About Us - ICDL (ICDL Africa)

Rwanda - ICDL (ICDL Africa)

DigiSchool - ICT Authority

DigiSchool – ICT Authority - ICT Authority

Home - ICT Authority

Kenya Open Data - ICT Authority

(Mis)allocation of teachers and state capacity - IGC - International Growth Centre (IGC)
Cross-country differences in educational attainment are large. Despite a massive expansion of primary schooling in developing countries in the last decades, a substantial share of the population in low-income countries still does not complete primary education. Since teachers are a key input into the education process and teacher compensation constitutes a major part of public […]

Household Income Expenditure Surveys (HIES) - ILO

Sierra Leone - Imagine Worldwide (Imagine Worldwide)

InfoTimor - InfoTimor

How to become an independent learner - InnerDrive
Independent learning is the holy grail of education. Here's what it looks like and how students can become independent learners.

Education technology | INEE - Inter-Agency Network for Education in Emergencies
Keywords: ⛔ No INSPIRE recid found

INEE Minimum Standards - Inter-agency Network for Education in Emergencies (INEE) (2024)

About IGWG | IGWG - Interagency Gender Working Group (IGWG)

Inclusive curriculum - International Bureau of Education

Every Adolescent Girl Empowered and Resilient (EAGER) - International Rescue Committee (IRC)
A project designed to create accessible and empowering learning opportunities for out-of-school adolescent girls in Sierra Leone, strengthening their knowledge, skills, and agency to shape their lives.

Affordability - International Telecommunication Union
Affordability - backgrounder
Keywords: ⛔ No INSPIRE recid found

Digital Development Dashboard - International Telecommunication Union (ITU)

"Digital Senegal 2025" Strategy - International Telecommunications Union

Basic e-Learning Library (BeLL) : Free Texts : Free Download, Borrow and Streaming : Internet Archive - Internet Archive

Africa Internet Users, 2020 Population and Facebook Statistics - Internet World Stats: Usage and Population Statistics

Students with Significant Cognitive Disabilities - IRIS Center
Keywords: ⛔ No INSPIRE recid found

Exercise B: How to do random assignment using MS Excel - J-PAL (Abdul Latif Jameel Poverty Action Lab)

Report for EdTechHub (ODI) - Joynes, Chris; Gibbs, Emma
Keywords: ⛔ No DOI found

What’s working? What isn’t? - Joynes, Chris; Gibbs, Emma; Sims, Kate
Keywords: ⛔ No DOI found

Laptops lie idle in schools on lack of skilled tutors - July 25 2018, Wednesday (Business Daily)
Lower primary public school teachers are not using technology in classrooms due to computer illiteracy.

JABSOM Library: Colandr for Systematic Reviews: Introducing Colandr - Kahili-Heede, Melissa
Using the systematic review tool for title and abstract screening, full-text article screening, and data extraction

KaiOS Home - KaiOS (KaiOS)
the mobile OS for smart feature phone to enable tomorrow

KaiOS Home - KaiOS (KaiOS)
the mobile OS for smart feature phone to enable tomorrow

Education and distance learning gaming platform - KarMuqabla
Helping student education by letting them test themselves against hundreds of thousands of their peers through our innovative syllabus-based gaming software

KCSE Biology Syllabus 2022/2023 - KCSE

A Co-design Methodology for Blended Teacher Professional Development in Contexts of Mass Displacement.pdf - Kennedy, E; Moghli, MA; Chase, E; Pherali, T; Laurillard, D
Teachers working in challenging contexts of mass displacement need both expert and peer support. This article shares a co-design methodology being used to develop and test the use of what we are calling Massive Online Open Collaborations (MOOCs) which involve blended learning approaches for teacher professional development
Keywords: Google Scholar/ teacher "professional development" AND refugees AND technology; RER theme_supporting educators

Kenya Disabiliy Resource | Special Educational Needs - Kenya Disability Resource

CBC Materials - Kenya Institute of Curriculum Development

Curriculum Designs(PP1-Grade4) - Kenya Institute of Curriculum Development

Popular Slides on CBC - Kenya Institute of Curriculum Development

Kenya Kwanza Plan - Kenya Kwanza (Kenya Kwanza Plan)
Kenyans are rightfully skeptical of lofty promises and seemingly well-crafted plans that never get implemented. We have developed this plan well aware that it will stand or fall on the how question. There are three tests that a good plan must pass, namely prioritisation, sequencing and financing.

Equalisation Fund Bill, 2022 | The Kenyan Parliament Website - Kenya Parliament

Social Pillar - Kenya Vision 2030

Lao People's Democratic Republic's Constitution of 1991 With Amendments Through 2015 - Khamphaeng, Phochanthilath
Translated by Miss Khamphaeng Phochanthilath as part of the research project “Constitutional Pluralism in Southeast Asia'' funded by the Centre for Asian Legal Studies, Faculty of Law, National University of Singapore, with edits by the Comparative Constitutions Project. This complete constitution has been generated from excerpts of texts from the repository of the Comparative Constitutions Project, and distributed on constituteproject.org.

Meet Khanmigo: Khan Academy's AI-powered teaching assistant & tutor - Khanmigo
Khanmigo, built by nonprofit Khan Academy, is a top-rated AI for education. Save time on prep, tackle homework challenges, and get personalized tutoring.

Michael G. Findley University of Texas, Austin - Kikuta, Kyosuke; Denly, Michael
External validity captures the extent to which inferences drawn from a given study’s sample apply to a broader population or other target populations. Social scientists frequently invoke external validity as an ideal, but they rarely attempt to make rigorous, credible external validity inferences. In recent years, methodologically-oriented scholars have advanced a ﬂurry of work on various components of external validity, and this article reviews and systematizes many of those insights. We ﬁrst clarify the core conceptual dimensions of external validity and introduce a simple formalization that demonstrates why external validity matters so critically. We then organize disparate arguments about how to address external validity by advancing three evaluative criteria: Model Utility, Scope Plausibility, and Speciﬁcation Credibility. We conclude with a practical aspiration that scholars supplement existing reporting standards to include routine discussion of external validity. It is our hope that these evaluation and reporting standards help re-balance scientiﬁc inquiry, such that the current obsession with causal inference is complemented with an equal interest in generalized knowledge.
Keywords: ⛔ No DOI found

Navigating the Shifting Sands of Online Safety - Kingsley, Al (GESS Education)
All independent online activities expose young people to risks, regardless of what device they’re on, so what’s the answer to shielding them from the dangers?

Kiwix: Internet content for people without internet access! - Kiwix (Kiwix)
Read Wikipedia or any website on your mobile phone or computer, even when there is no internet. For free!

Our Success Story: Academic Bridge - kLab

KoBoToolbox | Data Collection Tools for Challenging Environments - KoBo Toolbox (KoBoToolbox)
KoBoToolbox is a suite of tools for field data collection for use in challenging environments. Our software is free and open source. Most of our users are people working in humanitarian crises, as well as aid professionals and researchers working in developing countries.

Kolibri : A Free, Open Source Education for All | Learning Equality - Kolibri (https://learningequality.org/kolibri/)

Komuniti Guru Digital Learning - Komuniti Guru Digital Learning

Primary teacher education in Malawi: Insights into practice and policy - Kunje, D et al
Keywords: ⛔ No DOI found

Primary teacher education in Malawi: Insights into practice and policy - Kunje, D et al
Keywords: ⛔ No DOI found

Primary teacher education in Malawi: Insights into practice and policy - Kunje, D et al
Keywords: ⛔ No DOI found

About Us – Kytabu - Kytabu

Kytabu Super School – Kytabu - Kytabu

Resolution No. 28/NQ-CP dated March 03, 2021 on issuance of national strategy for gender equality in 2021 - 2030 28/NQ-CP,Nghị quyết 28 2021 - LawNet
Resolution No. 28/NQ-CP dated March 03, 2021 on issuance of national strategy for gender equality in 2021 - 2030 28/NQ-CP,Nghị quyết 28 2021

Design Based Implementation Research - LearnDBIR

Kolibri : A Free, Open Source Education for All | Learning Equality - Learning Equality

The Learning Passport - Learning Passport

Enketo - LLC), Martijn van de Rijdt (Enketo
Enketo Open-Source Project for the ODK ecosystem: OpenRosa Enketo.

Malawi - LNGB Consortium

Longhorn eLearning Website - Longhorn Publishers PLC

Can Nudge Messaging Positively Influence School Attendance? - Longley, Sophie (EdTech Hub)
In Northern Ghana, Wunni Sabo's decision to prioritise his daughter's education, inspired by nudge messaging, is helping to spark a movement for learning. Click to read this story of change.

M-Shule - M-Shule
M-Shule is an SMS knowledge-building platform that helps organizations deliver Learning, Evaluation, Activation, and Data tools across East Africa.

Bangladesh GNI per capita 1973-2021 - Macrotrends
GNI per capita (formerly GNP per capita) is the gross national income, converted to U.S. dollars using the World Bank Atlas method, divided by the midyear population. GNI is the sum of value added by all resident producers plus any product taxes (less subsidies) not included in the valuation of output plus net receipts of primary income (compensation of employees and property income) from abroad. GNI, calculated in national currency, is usually converted to U.S. dollars at official exchange rates for comparisons across economies, although an alternative rate is used when the official exchange rate is judged to diverge by an exceptionally large margin from the rate actually applied in international transactions. To smooth fluctuations in prices and exchange rates, a special Atlas method of conversion is used by the World Bank. This applies a conversion factor that averages the exchange rate for a given year and the two preceding years, adjusted for differences in rates of inflation between the country, and through 2000, the G-5 countries (France, Germany, Japan, the United Kingdom, and the United States). From 2001, these countries include the Euro area, Japan, the United Kingdom, and the United States.

Vietnam Life Expectancy 1950-2024 - Macrotrends (Macrotrends)
Chart and table of Vietnam life expectancy from 1950 to 2024. United Nations projections are also included through the year 2100.

Makhalidwe Athu - Makhalidwe Athu
All Stories must be less than 480 characters

upSCALE - Malaria Consortium

Education Sector Plan - Malawi; Sierra Leone

Remarks by World Bank Group President David Malpass on G20 Finance Ministers Conference Call on COVID-19 - Malpass, David (World Bank)
World Bank Group President David Malpass issued his remarks from the G20 Finance Ministers conference call on the COVID-19 pandemic.

GAGE Rigorous Review Girls' clubs, life skills programmes and girls' well-being outcomes - Marcus, Rachel; Gupta-Archer, Nandini; D'Arcy, Madeleine; Page, Ella (GAGE Rigorous Review, 2017)
This rigorous review synthesises studies on the empowerment impacts of girls’ clubs and life skills programmes with a gender equality focus. Girls’ clubs, or youth development clubs, have become an increasingly common component of school-based and community-based programmes that aim to improve capability outcomes and broader wellbeing of girls in developing countries. While some in the development community are enthusiastic about the potential of such clubs to empower girls, others raise questions about their impact, reach, sustainability and cost-effectiveness. The review, the first of its kind to synthesise existing evaluations of girls’ clubs, finds substantial evidence of the positive impact of these programmes, particularly around changes in discriminatory gender norms and practices. It also highlights remaining programming and knowledge gaps.

School and District Data - Massachusetts Department of Elementary and Secondary Education - Massachusetts Department of Elementary and Secondary Education

Hanga Ahazaza 'Create the Future' in Rwanda - Mastercard Foundation (Mastercard Foundation)
Hanga Ahazaza is a five-year Mastercard Foundation initiative focused on increasing employment opportunities for young people in the tourism and hospitality sector in Rwanda.

Mathshop - Mathshop

Education for children with disabilities - improving access and quality - Mattingly, Jacqui; McInerney, Laura (Department for International Development)

Down syndrome – Symptoms and causes - Mayo Clinic (Mayo Clinic)
Down syndrome is a genetic disorder caused when abnormal cell division results in extra genetic material from chromosome 21.
Keywords: ⛔ No INSPIRE recid found

Education Data Dictionary - MBSSE

Sao Paulo Media Center - Media Center

Radio Market in Ghana - Media Ownership Monitor: Ghana (Media Ownership Monitor)
Radio is the most prevalent media in Ghana: a huge number of 481 FM broadcasting stations are authorized, out of which 354 stations...

Resources - mEducation Alliance (Mobiles for Education Alliance)
Landscape Reviews and Other Resources Landscape reviews and other resource materials have been compiled by various members of the mEducation Alliance or other stakeholders to give snapshots of a range of ICT4E projects and interventions. Crisis and Conflict Situations Covid-19 Read more ›

Resources - mEducation Alliance (Mobiles for Education Alliance)
Landscape Reviews and Other Resources Landscape reviews and other resource materials have been compiled by various members of the mEducation Alliance or other stakeholders to give snapshots of a range of ICT4E projects and interventions. Crisis and Conflict Situations Covid-19 Read more ›

Let’s Chat: Chatbot Nudging for Improved Course Performance - Meyer, Katharine; Page, Lindsay C.; Smith, Eric; Walsh, B. Tyler; Fifield, C. Lindsey; Evans, Michael
Despite documented benefits to college completion, more than a third of students who initially enroll in college do not ultimately earn a credential. Completing college requires students to navigate both institutional administrative tasks (e.g., registering for classes) and academic tasks within courses (e.g., completing homework). In postsecondary education, several promising interventions have shown that text-based outreach and communication can be a low-cost, easy to implement, and effective strategy for supporting administrative task navigation. In this paper, we report on two randomized controlled trials testing the effect of a text-based chatbot with artificial intelligence (AI) capability on students' academic task navigation in introductory courses (political science and economics). We find the academic chatbot significantly shifted students’ final grades, increasing the likelihood students received a course grade of B or higher by 5-6 percentage points and reduced the likelihood students dropped the course.

SWOT Analysis - Mind Tools Content Team (MindTools)

Se lanza Aprendo En Línea Docente para reforzar el aprendizaje remoto - mineduc

Politique sectorielle: Faire du Togo un hub de services et un centre international d’innovation et de compétence digitale - Ministère de l'Economie et des Finances (Ministère de l'Economie et des Finances)
Faire du Togo un hub de services et un centre international d’innovation et de compétence digitale Les technologies de l’information et de la communication (TIC) sont aujourd’hui omniprésentes dans tous les secteurs de l’économie. Partout dans le monde, on assiste à une transformation profonde dans la manière dont ces technologies impactent les rapports humains et […]

SIMEN | - Ministère de l’Éducation National

Covid 19, le ministère de l'Education lance l'initiative "APPRENDRE À LA MAISON" | Ministère de l’Education nationale - Ministère de l’Education Nationale

Division de la Radio – Télévision scolaire (DRTS) - Ministère de l’Education Nationale

Programme d’Amélioration de la Qualité, de l’Équité et de la Transparence – Transparence –Education / Formation (PAQUET – EF) - Ministère de l’Éducation Nationale, et al.

2021 Annual Schools Census Data. - Ministry of Basic and Senior Secondary Education.

Leh Wi Lan | MBSSE - Ministry of Basic and Senior Secondary Education: Sierra Leone

Education Sector Strategic Plan (2018/19 to 2023/24) - Ministry of Education (Republic of Rwanda)

Education Reform - Ministry of Education, Ghana

Education Sector Analysis - Ministry of Education, Ghana (2018)

Education Sector Analysis - Ministry of Education, Ghana (Ministry of Education (Ghana), 2018)

Education Strategic Plan, 2018–2030 - Ministry of Education, Ghana (2018)

Education Strategic Plan 2018-2030 - Ministry of Education, Ghana (Government of Ghana, 2018)

Secondary Biology Form One: Student Book - Ministry of Education & Higher Studies (Republic of Somaliland)

Education Ministry, JICA Launch Think! Think! Free Online Classes - Ministry of Education, Youth and Sport
There is no translation available.Ministry of Education, Youth and Sports (MoEYS) in cooperation with Japan International Cooperation Agency (JICA) ha...

Ministry of Education, Youth and Sport Cambodia - YouTube - Ministry of Education, Youth and Sport Cambodia

AEPAM Online Library - Ministry of Federal Education & Professional Training

Distance Learning in Pakistan Through Policy Intervention: National Distance Learning Framework. - Ministry of Federal Education & Professional Training

Equitable Access to Education for Children with Disabilities - Mishra, Anant (EdTechReview)
Assistive Technology (AT) broadly categorizes the physical tools that support children with disabilities. Assistive Technology devices range..

Frontier AI LLMs, assistants, agents, services - Mistral AI
The most powerful AI platform for enterprises. Customize, fine-tune, and deploy AI assistants, autonomous agents, and multimodal AI with open models.

How Sierra Leone is betting on data to fight the impact of climate change on schools - Momoh, Adamah; Atherton, Paul (Global Partnership for Education, 2022)
Data can significantly improve decision-making and allow for prioritizing interventions to benefit the most vulnerable populations. That’s why the ministry of Education in Sierra Leone is working with Fab Inc. to develop a web-based data tool that helps estimate and prioritize where new schools are really needed.

Movva - Movva

Mtabe – Just Ask Too. - Mtabe

Mtabe – Q&A SMS eLearning Platform - Mtabe

Developing multimedia enhanced content to upgrade subject content knowledge of secondary school teachers in Tanzania - Mtebe, Joel S; Kibga, Elia Y; Mwambela, Alfred A; Kissaka, Mussa M (Journal of Learning for Development, 2015)
The failure rates and lack of interest amongst students in science and mathematics in secondary schools in Tanzania is a serious problem. The Ministry of Education and Vocational Training (MoEVT) implemented a project to enhance and upgrade the pedagogical knowledge and subject content knowledge of teachers in selected difficult topics in science and mathematics in secondary education. This article reports on the process involved in the development of multimedia enhanced content that involved teachers, facilitators, and technical staff. The developed content was evaluated for its satisfaction using a sample of 72 experts that included teachers and instructors after using the content for 10 days. Generally, respondents were satisfied with the quality of the developed multimedia enhanced content. However, accuracy had a minimum percentage of users’ satisfaction with 37%. This shows that the majority of the content had spelling and grammatical errors that were supposed to have been corrected before producing the final product. Although this is ongoing work, we believe that the lessons learned from our efforts can be useful to similar organizations planning to develop multimedia enhanced content for educational purposes.
Keywords: ⛔ No DOI found

Using SMS mobile technology to assess the mastery of subject content knowledge of science and mathematics teachers of secondary schools in Tanzania - Mtebe, Joel S.; Kondoro, Aron; Kissaka, Mussa M.; Kibga, Elia (International Journal of Educational and Pedagogical Sciences, 2015)
Using SMS Mobile Technology to Assess the Mastery of Subject Content Knowledge of Science and Mathematics Teachers of Secondary Schools in Tanzania
Keywords: ⛔ No DOI found

A critical review of eLearning research trends in Tanzania - Mtebe, Joel S.; Raphael, Christina (Journal of Learning for Development, 2018)
This study investigated research trends on eLearning implementation in Tanzania from 2007 to 2017. A total of 74 articles from electronic databases, conference proceedings, and selected electronic journals were reviewed. Using content analysis, the study found that there is an increasing interest in eLearning research with the majority of studies conducted by researchers from three universities. Students was found to be the most studied population group while quantitative research design being the most preferred research design. It was also revealed that mobile and game based learning were the least investigated eLearning technologies despite the proliferation of mobile telephony in Tanzania. Internet access and lack of support were the most ranked challenges hindering eLearning implementation in Tanzania. This study will also help policy makers to promote further research in areas where the research gaps have been identified and find interventions to overcome barriers that hinder eLearning implementation in Tanzania.
Keywords: ⛔ No DOI found

Eliciting in-service teachers’ technological pedagogical content knowledge for 21st-century skills in Tanzania - Mtebe, Joel S; Raphael, Christina (Journal of Learning for Development, 2018)
The Tanzania Vision 2025 articulates the country's aspiration of becoming an industrialized and middle-income country by 2025. The education sector, which is the main driving force towards realizing this goal, is expected to bring about the right mix of high-quality skills for the rapid development of quality and adequate human resources. The kind of revolution needed is nevertheless impossible if teachers are not equipped with the necessary skills to bring in the desirable changes. This study adapted Technological Pedagogical Content Knowledge (TPACK) for 21st-Century skills to investigate teachers’ competence levels of 21st-Century skills using selfreported survey and classroom observations from a sample of 132 teachers in 20 schools in Pwani and Morogoro regions. The study found out that many teachers have moderate self-reported confidence in all TPACK elements with technology. Conversely, teachers self-reported confidence levels in content knowledge, pedagogical knowledge, and pedagogical content knowledge was found to be high. The findings from this study provides valuable insights on how teachers use ICT to prepare students for 21-Century skills capable of supporting the country’s efforts towards developing an industrial economy.
Keywords: ⛔ No DOI found

Determinants of Implementation of Public Sector Projects in Kenya: A Case of Laptop Project in Public Primary Schools in Kangundo Sub-County, Machakos County - Muinde, Samuel Mutisya
Keywords: ___working_potential_duplicate

Social Media Demographics - NapoleonCat. Stats
Facebook, Instagram, Linkedin and Messenger user demographics updated monthly for every country in the world.

Inicio - National Institute for the Deaf (Insor Educativo)

Population and Housing Census - National Institute of Statistics Rwanda

nawiripro | Karibu - Nawiripro

marginalised-girls - Naylor, Ruth; Gorgen, Kristine
Keywords: ⛔ No DOI found

Certificate of Secondary Education Examination (CSEE) Results - NECTA

Solutions To Learning Poverty - New Globe
Issuu is a digital publishing platform that makes it simple to publish magazines, catalogs, newspapers, books, and more online. Easily share your publications and get them in front of Issuu’s millions of monthly readers. Title: Solutions To Learning Poverty, Author: NewGlobe, Name: can_education_be_standardized_evidence_from_kenya, Length: undefined pages, Page: 1, Published: 2022-06-13

Mother tongue: A foundation for dreams - Nguyen, Hoang Anh; UNICEF Viet Nam; Cai, Doet Lao
Mother tongue – a foundation for dreams

Meta-Analysis of Gender Equity and Social Inclusion in Primary Education for Teachers in Tanzania: An Assessment of Current Status and Future Directions - Nkya, Henry

Launching the Development of an OER World Map: Phase II - North Rhine-Westphalian Library Service Centre (The William and Flora Hewlett Foundation)

Wiki Sign Dict: A Development of an Online Sharing Dictionary for Hearing Impaired. - Nuttaya, Iam-Khong; Surachai, Suksakulchai

O'Genius Panda - O'Genius Panda

Learning English Language by Radio in Primary Schools in Kenya - Odera, Florence Y
Radio is one of the most affordable educational technologies available for the use in education and development in developing countries. This article explores the use of school radio broadcast to assist teachers and pupils to learn and improve English language both written and spoken in Kenyan primary schools. English language occupies a central place in formal education in Kenya. It is one of the compulsory subjects in both primary (aged six to 13 years) and secondary education (aged 14 to 18 years). It is also a medium of instruction in upper primary from standard four to university education in Kenya. However, teaching and learning English remains one of the most difficult and taxing assignment to primary schoolteachers, because when children join class one they go to the classroom with pre-set language skills. They have developed skills in their vernacular which is the language of instruction in most of rural schools or Kiswahili in urban schools. Sometimes, they mix vernacular, Kiswahili and English and come up with another language called “Sheng”. This makes it very difficult for them to learn English language. Research from developed and developing countries indicates that the use of school radio programmes assist pupils and teachers to learn foreign language like English faster and help them to improve pronunciation of difficult words. School radio broadcast was introduced in Kenya in 1961. One of the reasons was to help improve the standard of spoken and written English language and set the standard for the spoken English in the country. Radio was chosen, because it is affordable and simple to maintain. Despite of the existence of the program in Kenya for many years, there has been an out cry over falling standard in English language evidenced by poor performance in national examinations. The purpose of this study was to find out if teachers in primary schools use broadcasts to schools radio programmes to assist them in teaching and learning the language. The study was based on a descriptive survey. The area of study was Kisumu district and saturated sampling technique was used to select a sample of participants. Data were collected by use of questionnaire for pupils and teachers, while semi-structured interview was used to collect information from head teachers. The main findings indicated that most teachers were not listening to the school radio broadcasts. Very few of them used radio lessons citing various problems, such as lack of resources, broadcast time tables and teachers guide notes, negative attitudes and large number of pupils in the class. Those, who listened to English radio lessons, valued them very much and noted how it has helped to improve the pupils spoken English and performance in Kenya certificate of primary education examination. In view of the findings, the paper recommends that head teachers should provide teachers with radio sets and support materials, encourage and assist them to use English radio lessons.
Keywords: ___working_potential_duplicate; ⛔ No DOI found

Data-driven innovation for growth and well-being - OECD
Data and research on e-commerce including measuring the information economy, internet economy outlook, open internet, openness, key ICT indicators, digital economy policy papers., Greater access and use of data creates a wide array of policy issues, such as privacy and consumer protection, open data access, skills and employment, and measurement to name a few. The OECD is undertaking extensive analysis on the role of data in promoting innovation, growth and well-being.

Data Governance, Privacy and Digital Security - OECD
Data and research on e-commerce including measuring the information economy, internet economy outlook, open internet, openness, key ICT indicators, digital economy policy papers., The global and interconnected digital environment offers a wide range of social and economic benefits and generates enormous potential by fostering innovation, productivity and new sources of growth. Data governance, privacy and digital security are key issues at the heart of OECD work on trust in the digital economy.

Viet Nam Teachers and teaching conditions, primary to upper secondary education - OECD (Education GPS)

OER Courseware, Research and Policies | OER Africa - OER Africa

OER Commons - OER Commons (OER Commons)

Creative Commons — Attribution-NonCommercial 3.0 Unported — CC BY-NC 3.0 - OER World Map

OER World Map - OER World Map

ICT education for girls provides the bandwidth for a more robust digital society | United Nations in Thailand - Okuda, Atsuko (United Nations Thailand)
Closing the gender gap in education outcomes has not translated into equal participation and representation in politics, the economy and society in Thailand.
Keywords: ⛔ No INSPIRE recid found

Open Learning Exchange | Moving from education to learning - OLE

http://www.oleghana.org/index.php - OLE Ghana

onebillion: one app that delivers reading, writing and numeracy - Onebillion

onebillion: one app that delivers reading, writing and numeracy - onebillion

onebillion: onecourse – one app for reading and numeracy - onebillion

Context and Appropriate Technology: The Unavoidable Partnership - Onguko, Brown (2012)
Keywords: ⛔ No DOI found

Open Data Commons: legal tools for open data - Open Knowledge Foundation

Ghana Reads - Open Learning Exchange

Open Learning Exchange: Moving from education to learning - Open Learning Exchange

Our Platform | Open Learning Exchange - Open Learning Exchange

OpenAlex: The open catalog to the global research system - OpenAlex
Keywords: _Added-ailr-2024

Taleemabad - Orenda Project

Innovative Research Methodologies: Participatory Ethnographic Evaluation Research (PEER). - Oyinloye, Bukola
This podcast is the third in a series commissioned by the Research Methodology in Education Special Interest Group to showcase the variety of methodologies and methods being undertaken by...

Home - P2PU

Is Technology the Panacea and are we using it? - Pakistan Institute of Development Economics

Introducing ICAN (International Common Assessment of Numeracy)- as a Global Learning Metric - PAL network

Nesta: The Collective Intelligent Design Playbook - Peach, Kathy; Berditchevskaia, Aleks; Bass, Theo (Nesta)

Miya Miya - Pedago

Taleem Ghar: An initiative by Government of the Punjab - PITB

Plan Ceibal - Plan Ceibal

The Ed-Tech Space Pakistan 2020 - Planet N

Unlocking Learning: The Use of Education Technology to Support Disadvantaged Children’s Language Learning and Social Inclusion in Italy - Poleschuk, Svetlana; Dreesen, Thomas; D’Ippolito, Barbara; Lozano, Joaquin Carceles Martinez (UNICEF Innocenti - Global Office of Research and Foresight, 2023)

Unlocking Learning: The Use of Digital Learning to Support the Education and Inclusion of Refugees and Migrant Children in Bosnia and Herzegovina - Poleschuk, Svetlana; Soldo, Andrea; Dreesen, Thomas (UNICEF Innocenti - Global Office of Research and Foresight, 2023)
In Bosnia and Herzegovina, the number of refugees and migrants arriving in the country has increased from just a few dozen arrivals annually prior to 2017 to 95,000 between 2018 and 2022. This increase has put incredible strain on the country's education systems. This research presents critical findings on the implementation and effectiveness of the Akelius digital learning application in Bosnia and Herzegovina, which was introduced as a tool to support refugee and migrant children's English and German language learning. The findings demonstrate that using the digital application in a blended learning approach in classrooms was especially useful for personalizing learning and supporting children with diverse learning levels and needs. The report also explores the challenges faced, and good practices to tangibly improve the implementation of digital learning in classrooms.
Keywords: Access to Education; Barriers; Best Practices; Blended Learning; Computer Software; Elementary School Students; Elementary School Teachers; English (Second Language); Faculty Development; Foreign Countries; German; Handheld Devices; Immigrants; Individualized Instruction; Learning Activities; Learning Motivation; Outcomes of Education; Partnerships in Education; Pedagogical Content Knowledge; Program Effectiveness; Refugees; Second Language Instruction; Second Language Learning; Student Attitudes; Student Needs; Teacher Attitudes; Teaching Methods; Technological Literacy; Technology Integration

The Teachers’ Portal as a Tool for Teachers’ Professional Development in Bangladesh - Prime Minister's Office: Bangladesh (Access to Information Programme: Government of the People's Republic of Bangladesh; UNDP; USAID)

Principles for Digital Development - Principles for Digital Development (Principles for Digital Development)
Resources & Expertise for the Digital Principles
Keywords: ___working_potential_duplicate; ⛔ No INSPIRE recid found

Principles of Digital Developmeent - Design for Scale - Principles for Digital Development (Principles for Digital Development)
Achieving scale requires adoption beyond an initiatives pilot population and often necessitates securing funding or partners that take the initiative to new communities or regions.

Welcome To PEF Foundation Assisted Schools - Punjab Education Foundation

eLearn App for Android - Punjab IT Board (Download.com)
eLearn.Punjab is an Educational app for an official repository of digitized textbooks of Punjab. Each book has been augmented with Video Lectures,

Punjab School Monitoring - Punjab School Monitoring

Modelling Factors Influencing Digital Readiness: A Case of Teachers in Ghana’s Basic School System - Quaicoe, James Sunney; Pata, Kai (Springer International Publishing, 2015)
This study explored the factors involved in developing teachers’ digital readiness towards ICT integration in basic schools. A survey with teachers in the Western Ghana was carried out; a sample (N = 85) teachers from 17 schools selected from the urban, peri-urban and rural areas participated. We used Valsiner’s Zone of Free Movement (ZFM) and Zone of Promoted Action (ZPA) to model the factors in which teachers’ digital readiness is formed as the final level of Vygotsky’s Zone of Proximal Development (ZPD). In our hypothetical model, ZFM comprised factors related with surrounding ICT environment in schools, and teachers’ culturally defined predispositions related to ICT use and issues; ZPA an intervention-related factor projected teacher actions within ZFM to facilitate learning in the range of ZPD. The hypothesised model was evaluated with SEM-Path analysis – using regression analysis. The final path model indicated that the ZFM factors related with ICT environment in schools and the culturally defined predispositions related to ICT use; constrained the intervention-related ZPA factor that in turn has impact on teachers’ digital activities. In addition, ZFM factors directly influenced at what level of digital knowledge, -application, -skills and -confidence teachers arrived, and what their projections in using ICT were in the final stage of ZPD.
Keywords: ICT integration; Teacher digital readiness; ZFM; ZPA; ZPD

The Teachers’ Digital Literacy: Determining Digital Divide in Public Basic Schools in Ghana - Quaicoe, James Sunney; Pata, Kai (Springer International Publishing, 2015)
This study explored the role of the teacher’s digital literacy (TDL) among other schools’ digital culture (SDC) components in determining Digital Divide (DD) among Ghana’s basic schools. A paper-based survey was conducted with teachers and head-teachers from randomly sampled 17 basic schools in various locations in Ghana. The questionnaire was adopted from the Institute for Capacity Building – UNESCO and EU rubrics for measuring ICT in education; and explored nine Digital Culture components including TDL. Data were analysed using K-means Clustering, Correlation analysis, Discriminant analysis, and Independent-samples T-test. The schools were clustered based on SDC components into two DD groups; the principal influencing factors were Teachers’ digital literacy and ICT related policy documents. The school groups particularly differed based on whether they not only had the digital literacy competences, but also applied these competences in their teaching and professional development in schools. We argue that in spite of training for TDL, many schools still lack other digital culture components, and this may hinder them in applying ICT in their schools.
Keywords: Digital divide; Digital literacy; Information literacy; School digital culture; Teacher digital literacy

Home - Queen Rania Foundation

Rising Network Academies - RAN

Raspberry Pi Foundation - About Us - Raspberry Pi (Raspberry Pi)
The Raspberry Pi Foundation is a UK-based charity that works to put the power of digital making into the hands of people all over the world.

Teach, Learn, and Make with Raspberry Pi – Raspberry Pi - Raspberry Pi

Responsible Data for Children: Principles - RD4C (Responsible Data for Children)

Empowering emerging tech leaders - Re:Coded

REACH2025: Jordan’s Digital Economy Action Plan - REACH2025

Research Solutions Announces Acquisition of scite - Research Solutions
Research Solutions announces their acquisition of scite, a search and discovery platform leveraging AI to increase the discoverability and evaluation of research.

The Coaching Approach - Results for Development

Introducing Systems Approaches - Reynolds, Martin; Holwell, Sue
Keywords: ❓ Multiple DOI

Technology Acceptable Use Agreement - Ridgewood Public Schools (Ridgewood Public Schools)

Riiid - Riiid
Bring cutting-edge AI for democratization of quality education; Explore our AI solutions to get rid of “inefficiency,” “inconsistency,” and “inequality” in education.

Systems thinking | RISE Programme - RISE

Rising Academies - Rising Academies

Rising Academies - Rising Academies

Rising Academies - Rising On Air - Rising Academies (Rising Academies)

Rising Academies - Our Partners - Rising Academy Network (Rising Academies)

Rising Academies - Rising On Air - Rising Academy Network (Rising Academies)

Remote Learning During the Global School Lockdown: Multi-country lessons - Rodriguez, Maria; Cobo, Cristobal; Muñoz-Najar, Alberto; Sánchez Ciarrusta, Iñaki (World Bank Group)

Remote learning during the global school lockdown: multi-country lessons - Rodriguez, Maria; Cobo, Cristobal; Muñoz-Najar, Alberto; Sánchez Ciarrusta, Iñaki (World Bank Group)

Tangerine® – Mobile Learning Assessments Made Easy - RTI

Rumie Initiative - Rumie (Rumie Initiative)
Providing free learning for underserved communities

Rumie LearnCloud - Rumie
The World's Largest Repository of 100% Free Learning Content

Electrification Of Primary Schools - Rural Electrification and Renewable Energy Corporation

The 50 MW Garissa Solar Power Plant - Rural Electrification and Renewable Energy Corporation

Blockchain in schools and colleges - Rustagi, Nimish; Chakraborti, Anirban

Pakistan’s Award-winning Learning Apps for Kids - SABAQ

Free Videos & Tests, Grades K-12, Pakistan - Sabaq Foundation
Sabaq Foundation provides more than 14000 FREE video lectures and tests for grades K-12 Pakistani students. It was founded in 2012 as a non-profit Trust.

REPENSER L’ÉDUCATION ET LA PÉDAGOGIE DANS UNE PERSPECTIVE AFRICAINE - SAGAYAR, MOUSSA MOHAMED; AKKARI, ABDELJALIL; GANDOLFI, STEFANIA
Keywords: ⛔ No DOI found

Using System Dynamics to Model Student Interest in Science, Technology, Engineering, and Mathematics - Sanchez, H Alex; Wells, Brian; Attridge, Joanne M
This paper presents preliminary results of a Raytheon project that uses systems dynamics to understand the intricacies of the U.S. educational system and to assist in exploring the effects of policies and programs, with a goal of doubling the numbers of science, technology, engineering and mathematics (STEM) college graduates by 2015. Specifically, a system dynamics model has been developed, the initial version of which targets increasing the number of students both capable and interested in pursuing careers in STEM disciplines. A few scenarios have been analyzed that examine changes for improving student capabilities. Initial results provide insight into the value and viability of a few proposed policies and indicate that with continued research, model development, and analysis it will be possible to further assess proposed improvements in the U.S education system.
Keywords: ___working_potential_duplicate; ⛔ No DOI found

Developing and communicating your message - Save the Children; The Open University

Discover Scholarcy Features - Try it now! - Scholarcy (Scholarcy | The long-form article summariser)
Discover the innovative features of our cutting-edge tool designed to revolutionize the way students researcher study and summarize articles.

Sustainable Development Goal 4 (SDG 4) | Education within the 2030 Agenda for Sustainable Development - SDG-Education 2030 Steering Committee
Keywords: ___working_potential_duplicate; auto_merged

TVET Platform for SEA - SEA-VET

History of SEAMEO Members - SEAMEO

Data entry: towards the critical study of digital data and education - Selwyn, Neil (Learning, Media & Technology, 2015)
The generation and processing of data through digital technologies is an integral element of contemporary society, as reflected in recent debates over online data privacy, ‘Big Data’ and the rise of data mining and analytics in business, science and government. This paper outlines the significance of digital data within education, arguing for increased interest in the topic from educational researchers. Building on themes from the emerging sub-field of ‘digital sociology’, the paper outlines a number of ways in which digital data in education could be questioned along social lines. These include issues of data inequalities, the role of data in managerialist modes of organisation and control, the rise of so-called ‘dataveillance' and the reductionist nature of data-based representation. The paper concludes with a set of suggestions for future research and discussion, thus outlining the beginnings of a framework for the future critical study of digital data and education.

COMPRÉHENSION ÉCRITE... EN ROUTE VERS LE C1+ - Senprof Education

Ressources Numeriques - Senprof Education

Using technology for enhancing teaching and learning in Bangladesh: challenges and consequences - Shohel, M. Mahruf C.; Kirkwood, Adrian (Learning, Media and Technology, 2012)
The increasing use of media and technologies for enhancing teaching and learning is an important current trend to overcome the challenges of schooling and teacher training in the changing world. Many countries in the Global South are trying to adopt technologies in their school and teacher training systems to achieve the UN Millennium Development Goals. Though some recent research shows impacts of using technologies for enhancing teaching and learning in technology-poor contexts, no research actually addresses the challenges and difficulties associated with using the technologies in those specific contexts. This article presents interview data derived from secondary schools teachers in Bangladesh, in a context beset with many difficulties associated with technology use. In a pilot project, Apple iPods were introduced in 2009 to explore the challenges and consequences of using technology in schools. The data reveal the implications for the teachers’ professional development when they used the iPod as a multimedia player to access educational resources made available to support teaching and learning. This article has also thrown some light on current debates about using technologies for enhancing teaching and learning in technology-poor contexts.
Keywords: Bangladesh; THEME: Curriculum and resources; THEME: Open systems; THEME: Teacher Professional Development; _Source:Intuitive; teachers’ professional development; teaching and learning; technology; technology-poor contexts; the

Using technology for enhancing teaching and learning in Bangladesh: challenges and consequences - Shohel, M. Mahruf C.; Kirkwood, Adrian (Learning, Media and Technology, 2012)
The increasing use of media and technologies for enhancing teaching and learning is an important current trend to overcome the challenges of schooling and teacher training in the changing world. Many countries in the Global South are trying to adopt technologies in their school and teacher training systems to achieve the UN Millennium Development Goals. Though some recent research shows impacts of using technologies for enhancing teaching and learning in technology-poor contexts, no research actually addresses the challenges and difficulties associated with using the technologies in those specific contexts. This article presents interview data derived from secondary schools teachers in Bangladesh, in a context beset with many difficulties associated with technology use. In a pilot project, Apple iPods were introduced in 2009 to explore the challenges and consequences of using technology in schools. The data reveal the implications for the teachers’ professional development when they used the iPod as a multimedia player to access educational resources made available to support teaching and learning. This article has also thrown some light on current debates about using technologies for enhancing teaching and learning in technology-poor contexts.
Keywords: Bangladesh; THEME: Curriculum and resources; THEME: Open systems; THEME: Teacher Professional Development; _Source:Intuitive; teachers’ professional development; teaching and learning; technology; technology-poor contexts; the

School-based teachers’ professional development through technology-enhanced learning in Bangladesh - Shohel, M.; Mahruf, C.; Banks, Frank (Teacher Development, 2012)

Teacher Monitoring Pilot - Sierra Leone Education Attendance Monitoring System (SLEAMS)
A pilot project to monitor teacher attendance aimed at achieving better education outcomes in Sierra Leone.

Introducing Smart Teaching and Learning (INSTAL) - Sindh Education Foundation, Government of Sindh
SEF|Sindh Education Foundation government of Sindh Sindh Education Foundation (SEF), was established under the Sindh Education Foundation Act, 1992 as a semi-autonomous organization committed to educating and empowering children and communities towards social change by ensuring access to educational facilities and quality education. towards social change by ensuring access to educational facilities and quality education access to educational facilities and quality education.

About us - Siyavula

Our Work: Open Textbooks - Siyavula

Pricing | Siyavula - Siyavula

Teacher Monitoring Pilot - SLEAMS

Smart TXTBKS - Smart TXTBKS

SPARK schools - SPARK schools

Squirrel AI Home Page - Squirrel AI
Personalized learning for all students. The most advanced learning technology in the world is finally coming to a city near you.

PRISMA endorsers - Statement, PRISMA

Pakistan - StateUniversity.Com

About us - Storybooks Ghana - Storybooks Ghana

Storybooks Timor-Leste: Languages - Storybooks Timor-Leste

Suraad - Suraad

Mini-Grids Partnership - Sustainable Energy for All | SEforALL (Sustainable Energy for All | SEforALL)
The Mini-Grids Partnership is a consortium of over 320 like-minded mini-grid stakeholders interested in enhancing and complementing each other’s work through collaboration and coordination.

Swayam Prabha - Swayam Prabha
The SWAYAM PRABHA has been conceived as the project for using the(2) GSAT-15 transponders to run (34) DTH channels that would telecast high quality educational programmes on 24X7 basis.

Home - T-TEL - T-TEL

Learning Hub - T-TEL - T-TEL

Our Work - T-TEL - T-TEL

Welcome to Taleem Ghar - Taleem Ghar

Teaching at the Right Level - strengthening foundational skills - Teaching at the Right Level Africa (Teaching at the Right Level)

TéléEcole | La 1ere Télé Educative au Sénégal - télé-école

Fiber Optics Lebanon - Telecommunications Regulatory Authority (Lebanon)

Welcome to TeleTaleem - TeleTaleem

TERNET - TERNET

OLCreate: TESS-India (Teacher Education through School-based Support) - TESS-India

About us | TESSA - TESSA

OLCreate: TESSA_GHA - TESSA - Ghana

8 Key Translation Technology Solutions - The Translation People
Create websites in different languages – CMS Translation Integration Plugins For companies looking to expand overseas, a localised website is one of the

ThinkZone India - ThinkZone

Rumie Build - Thomas, Jilson (Rumie Build)
Rumie Byte authoring application

COVID-19 and education systems in Tanzania: Brainstorming for a true ed-tech disruption? - Todd, Gemma (World Bank Blogs, 2020)
The world was already facing a ‘learning crisis’. The addition of school closures from the coronavirus (COVID-19) pandemic has brought on new challenges. We witnessed a big ‘technology rush’ with the government and education stakeholders exploring solutions.

COVID-19 and the education systems in Tanzania: Brainstorming for a true ed-tech disruption? (Part II) - Todd, Gemma (World Bank Blogs, 2020)
In Tanzania we have now opened all schools, colleges and universities, and we are hopefully going to stay in this post coronavirus (Covid-19) world. If we want technology to really revolutionize education the post Covid-19 world is a good time to make that happen.

Language data by country - Translators Without Borders (Translators without Borders)
LANGUAGE DATA BY COUNTRY 31 countries | 66 datasets | 90 maps

Language data for Nigeria - Translators Without Borders (Translators without Borders)
Open-source language data and maps about languages spoken in Nigeria can improve how we communicate with communities in crisis.

Language Data Initiative - Translators Without Borders

Tunapanda Institute - Tunapanda

Sauti za Wananchi - Twaweza.org

What is IVR (Interactive Voice Response)? - Twilio Docs
Interactive Voice Response (IVR) is an automated telephony system for callers using voice and touch-tones (DTMF). Also known as a phone tree.

Home - Ubongo Learning | African Children's Media & Edutainment - Ubongo

Toolkits Platform - Ubongo

UBONGO KIDS - Ubongo

Ubongo Learning - Ubongo (Ubongo)
Ubongo is Africa's leading children's edutainment and media company. As a non-profit social enterprise, Ubongo provides millions of families across Africa with fun, localised and multi-platform educational content that helps kids learn, and leverage their learning to change their lives.

Ubongo Kids - Ubongo Learning (Ubongo)
Ubongo Kids is our educational cartoon show that teaches 7 to 14-year-olds math, science & life skills through fun, animated stories & catchy, original songs. The show follows Kibena, Kiduchu, Koba, Baraka, Amani and their animal friends, as they go on adventures and solve problems in the fictional village of Kokotoa.

Learning from African classroom pedagogy to increase student engagement in education technologies - Uchidiuno, Judith; Yarzebinski, Evelyn; Keebler, Emily; Koedinger, Kenneth; Ogan, Amy (Association for Computing Machinery, 2019)
Tablet-based educational technologies provide a supplement to traditional classroom-based early literacy education, especially in regions with limited schooling resources. Prior work has probed how children generally interact with and learn from these technologies, however, there is limited research on student engagement with applications that utilize valuable input techniques such as automatic handwriting and speech recognition. In our study, we designed and field-tested early literacy speech and handwriting recognition applications with the primary aim of maximizing student engagement. We designed the applications based on prior research insights and classroom observations from our target population and field-tested the applications with 283 children living in rural Tanzania. We found that observing a small set of classrooms can produce design insights that increase engagement on tablet-based learning systems on a much larger scale. We also demonstrate the importance of domain familiarity in students' choice to persist through activities while learning with technology.
Keywords: early literacy; educational technologies; handwriting recognition; speech recognition; sub-saharan africa

The effectiveness of publicly vs. privately assigned group leaders among learners in rural villages in Tanzania - Uchidiuno, Judith; Yarzebinski, Evelyn; Vargas-Vite, Emilio; Koedinger, Ken; Ogan, Amy (International Society of the Learning Sciences (ISLS), 2019)
Keywords: ⛔ No DOI found

Country Fact Sheet | UN Women Data Hub - UN Women
Keywords: ⛔ No INSPIRE recid found

2019–2021 ICT Project Final Report - UNDP

Human Development Reports: Tanzania - UNDP

JP Malawi Girls' Education | MPTF Office - UNDP

(untitled) - UNESCO

Assessment for improved learning outcomes - UNESCO

Cumulative disadvantage; inter- and within-group inequalities | UNESCO Inclusive Policy Lab - UNESCO (UNESCO Inclusive Policy Lab)

Distance Learning - UNESCO

Education Sector Analysis - UNESCO

Educational Management Information System (EMIS) - UNESCO (Learning Portal)

Endline Study Report for Can't-Wait to Learn (CWTL) programme in Refugee Settlements in Uganda - UNESCO

Global Education Coalition facilitates free internet access for distance education in several countries - UNESCO (UNESCO, 2020)
Keywords: ___working_potential_duplicate

Module 3: Improving Education Management Information Systems (EMIS) - UNESCO

Professional Development for Teachers for Blended Learning and Online Strategies - Pilot Project - UNESCO (2020)

Technology | Education Profiles - UNESCO

Training materials in educational planning, administration and facilities, no. 1, 1982-no. 17, 1985 - UNESCO Digital Library - UNESCO

UIS Statistics - UNESCO

UNESCO Data for the Sustainable Development Goals: Bangladesh - UNESCO

UNESCO figures show two thirds of an academic year lost on average worldwide due to Covid-19 school closures - UNESCO (2021)

UNESCO targets teachers to improve distance and online learning in Zimbabwe - UNESCO (UNESCO, 2021)

World Inequality Database on Education (WIDE): Vietnam - UNESCO
The World Inequality Database on Education (WIDE) highlights the powerful influence of circumstances, such as wealth, gender, ethnicity and location, over which people have little control but which play an important role in shaping their opportunities for education and life.

Sierra Leone - UNESCO Institute for Statistics
...

UIS Statistics - UNESCO Institute for Statistics
Keywords: ⛔ No INSPIRE recid found

United Republic of Tanzania - UNESCO Institute of Statistics

Libya: How to use KoBo for UNHCR - UNHCR

Accessible Digital Learning Portal - UNICEF (Accessible Digital Learning Portal)
Welcome The Accessible Digital Learning Portal is a hub for technology focused information, content, tools, products and resources that support disability inclusive education in remote and classroom settings. This site provides resources for the production, distribution and implementation of accessible digital content and tools in high and low-resource environments and provides solutions that address user […]

Can broadcast media foster equitable learning amid the COVID-19 pandemic? - UNICEF (Evidence for Action, 2020)
This post is the second in a series of articles focused on helping children continue to learn at home during the COVID-19 global pandemic, emphasizing the need for multiple remote learning platforms to meet the needs of all students.   As discussed in the first post in this series on the impact of the COVID-19 pandemic, school closures around the globe mean that remote learning is now the only option for more than 1.3 billion children across 177 countries. MICS6 data reveal that many of the world’s children do not have internet access at home, particularly among poorer households. In response,…

Data Must Speak - UNICEF
User-friendly data empower decision makers to improve education for all children.

Education: Access to education and marketable skills remains a challenge for children in Sierra Leone - UNICEF
UNICEF works with the Government to provide access to education and marketable skills for Out-Of-School Children in Sierra Leone

Education | UNICEF Lao People's Democratic Republic - UNICEF
Keywords: ⛔ No INSPIRE recid found

Gender equality | UNICEF Lao People's Democratic Republic - UNICEF
Harnessing girls' power, energy, and creativity for a better future for all
Keywords: ⛔ No INSPIRE recid found

Guidance: assessing and monitoring learning during the COVID-19 crisis - UNICEF (Humanitarian Response, 2020)
This guidance note aims to help UNICEF Education staff, Ministry officials and partners reflect on how to take account of learning through meaningful formative and summative assessment practices during the COVID-19 pandemic. It highlights general considerations and key actions that teachers, schools and Ministries of Education can undertake in the area of assessment to ensure the continuity of quality learning throughout the COVID-19 pandemic.

Khang Panya Lao - UNICEF

Khang Panya Lao – MoES Teaching and Learning Platform - UNICEF
MoES Teaching and Learning Platform
Keywords: ⛔ No INSPIRE recid found

Malawian youths offer solutions to COVID-19 challenges in their communities - UNICEF (UNICEF, 2020)

Our lives online: Use of social media by children and adolescents in East Asia - opportunities, risks and harms - UNICEF (UNICEF, 2020)

Political economy analyses in countries in Eastern and Southern Africa: Case study – Tanzania mainland political economy analysis - UNICEF (2017)

Quality, continuity for primary education - UNICEF (UNICEF)

Remote learning during COVID-19: Factsheet - UNICEF (UNICEF)

Right Teachers, Right Places: Improving foundational learning through stronger teacher deployment - UNICEF

Strengthening the System: Investing in Sierra Leone's primary-level teachers for a sustainable future - UNICEF

Tanzania: The impact of language policy and practice on children’s learning: Evidence from Eastern and Southern Africa - UNICEF (UNICEF, 2017)

U-Report - UNICEF

UNICEF MICS - UNICEF

UNICEF Multiple Indicator Cluster Survey - UNICEF

Children with disabilities – Leave no one behind - UNICEF East Asia and Pacific (UNICEF for every child)
Keywords: ⛔ No INSPIRE recid found

Giga: Connecting Every School to the Internet - UNICEF Office of Innovation
Connecting Every School to the Internet

'Eskola Ba Uma’ initiative helps children continue learning in Timor-Leste - UNICEF Timor-Leste; Ministry of Education, Youth and Sport
Keywords: ⛔ No INSPIRE recid found

UN Convention on the Rights of the Child (UNCRC) - UNICEF UK (Unicef UK)
The United Nations Convention on the Rights of the Child (UNCRC) is the basis for all of Unicef's work and upholds children's rights all over the world.

Education Budget Brief 2020 - UNICEF; Government of Tanzania (2020)
Keywords: ⛔ No DOI found

Goal 4: Ensure inclusive and equitable quality education and promote lifelong learning opportunities for all - United Nations (Department of Economic and Social Affairs: Sustainable Development)

Goal 4 .:. Sustainable Development Knowledge Platform - United Nations

Historic New Sustainable Development Agenda Unanimously Adopted by 193 UN Members - United Nations (Historic New Sustainable Development Agenda Unanimously Adopted by 193 UN Members)
2015 - Time for Global Action for People and Planet

THE 17 GOALS | Sustainable Development - United Nations

Sustainable Development Goal 4 - United Nations Department of Economic and Social Affairs

Teacher Professional Development Programme Document - Universal Basic Education Commission

Université virtuelle du Sénégal – Première université publique numérique de l'Afrique de l'ouest - Université virtuelle du Sénégal (Université virtuelle du Sénégal)

The OER4Schools Professional Learning Resource - OER in Education - University of Cambridge: Faculty of Education

The OER4Schools Professional Learning Resource - OER in Education - University of Cambridge: Faculty of Education
Keywords: auto_merged

Unlocking Data - Unlocking Data Initiative

Pakistan 2022 Floods Response Plan: 01 Sep 2022 - 28 Feb 2023 (Issued 30 Aug 2022) - Pakistan | ReliefWeb - UNOCHA
Appeal in English on Pakistan about Agriculture, Coordination, Flash Flood, Flood and more; published on 30 Aug 2022 by OCHA

THE FUTURE OF LEARNING AND TECHNOLOGY IN DEPRIVED CONTEXTS - Unwin, Tim; Weber, Mark; Brugha, Meaghan; Hollow, David
This report addresses the future of basic education, Information and Communication Technologies (ICT) use in deprived locations, and the use of ICTs in primary school learning in 2020 and 2025, especially in deprived contexts. It draws on research evidence from the literature, the authors’ experiences of ICT use in education initiatives, interviews with practitioners and academics, a workshop, and consultations with Save the Children staff from many different countries, mostly conducted in August 2017.
Keywords: GENERAL - to be categorised; Google Scholar/ "refugee education" ICT

Urubuto - Urubuto

DREAMS: Partnership To Reduce Hiv/Aids In Adolescent Girls And Young Women | Global Health | U.S. Agency for International Development - USAID

Rapid Education and Risk Analysis (RERA) Toolkit - USAID
USAID’s EducationLinks is a resource for all education practitioners to learn and share knowledge to create and implement successful, effective education and skills development programs.

STATcompiler: the DHS Program - USAID

Technology for Data Collection Processing and Communication for EiE - USAID

The DHS Program - Quality information to plan, monitor and improve population, health, and nutrition programs - USAID

Ustad Mobile – Access and share education content offline - Ustad Mobile

Tools - Uwezo - Uwezo

Education, Equity and Inclusion: A policy paper for the G20 - Varkey Foundation (Varkey Foundation)

Scholarcy Summarizer Review: Pricing, Features, & More - Viraj, Mahajan
Ultimate Scholarcy summarizer review. 1. Working process 2. Pricing and plan 3. Technical details 4. Features and functionalities 5. Security and customer support 6. Pros and cons.

Prepaid tariffs - Vodacom Mozambique - Vodacom Mozambique

Sim Only Talk Deals| Vodacom Specials - Vodacom South Africa

Designing inclusive digital solutions and developing digital skills: guidelines - UNESCO Digital Library - Vosloo, Steve

Using technology to deliver high quality education | VSO - VSO

Refugee Education: is technology the solution? - Wagner, E
Keywords: RER theme_pedagogies and modalities

Child-centred Educational Radio Project in Kailahun District, Sierra Leone - Walker, David; Tristram, Bella; Pereznieto, Paola; Young, Tricia (United Nations Girls' Education Initiative; Overseas Development Institute)

State Management of Education Systems and Educational Performance - Walter, Torsten Figueiredo
Keywords: ⛔ No DOI found

Can't Wait To Learn - War Child
War Child empowers children and young people in conflict areas by providing psychosocial support, stimulating education and protecting children from the effects of war.

War Child Care System - Can't Wait to Learn | War Child - War Child Holland

We believe no child should be part of war. Ever. | War Child - War Child Holland

Inclusive and Equitable Education in Kenya – RELI - Wawira, Margaret

Nothing as Practical as Good Theory : Exploring Theory-Based Evaluation for Comprehensive Community Initiatives for Children and Families | Semantic Scholar - Weiss, Carol

Defining the "Open" in Open Content and Open Educational Resources - Wiley, David

Access to electricity (% of population) - Kenya | Data - World Bank

Bangladesh Data - World Bank

DataBank World Development Indicators - World Bank

Development Projects : Skills for A Vibrant Economy Project - P172627 - World Bank (World Bank)
Development Projects : Skills for A Vibrant Economy Project - P172627

Education statistics - all indicators | DataBank - World Bank

Fixed telephone subscriptions (per 100 people) - Rwanda | Data - World Bank

Ghana Accountability for Learning Outcomes Project - World Bank (2019)
Keywords: ___working_potential_duplicate

Ghana Accountability for Learning Outcomes Project - World Bank (2020)
Ghana Accountability for Learning Outcomes Project
Keywords: ___working_potential_duplicate

Ghana Accountability for Learning Outcomes Project. - World Bank (World Bank, 2019)

Ghana Secondary Education Improvement Project - World Bank (2020)
Ghana Secondary Education Improvement Project

Glossary | DataBank - World Bank

How countries are using edtech (including online learning, radio, television, texting) to support access to remote learning during the COVID-19 pandemic - World Bank (World Bank)
Examples of how countries are using edtech to support remote learning under COVID-19
Keywords: ___working_potential_duplicate

ID4D Practitioner’s Guide - World Bank

Implementation Status and Results Report - World Bank (2019)

Mobile cellular subscriptions (per 100 people) - Rwanda | Data - World Bank

Poverty and Shared Prosperity 2018 - World Bank (World Bank)
The Poverty and Shared Prosperity series provides a global audience with the latest and most accurate estimates on trends in global poverty and shared prosperity.

Procurement Details - World Bank (World Bank)

Senegal-Quality Improvement and Equity of Basic Education - AF - World Bank (World Bank)
Senegal-Quality Improvement and Equity of Basic Education - AF

Sierra Leone | Data - World Bank

TCData360 - World Bank

TCdata360: Households w/ personal computer, % - World Bank (TCdata360)
Percentage of households equipped with a personal computer

Teach - World Bank's Classroom Observation Tool - World Bank (World Bank)
Teach-Related Blogs

The World Bank DataBank - World Bank

The World Bank in Ghana - World Bank (World Bank)
The World Bank Group aims to help Ghana sustain economic growth, surpass the goal of halving poverty by 2015, and maintain its middle income status.

The World Bank in Tanzania - World Bank

The World Bank in Vietnam: Overview - World Bank
Vietnam’s shift from a centrally planned to a market economy has transformed the country from one of the poorest in the world into a lower middle-income country. Vietnam now is one of the most dynamic emerging countries in East Asia region.

The World by Income and Region - World Bank

Unemployment, female (% of female labor force) (national estimate) - Viet Nam, World Bank Open Data - World Bank
Free and open access to global development data

Unemployment, male (% of male labor force) (modeled ILO estimate) - Viet Nam, World Bank Open Data - World Bank
Free and open access to global development data

World Bank Country and Lending Groups - World Bank Data Help Desk - World Bank
Keywords: ⛔ No INSPIRE recid found

World Bank Data Catalog - World Bank

World Bank Open Data - World Bank
Free and open access to global development data

World Bank Open Data - World Bank (World Bank Open Data)
Free and open access to global development data

World Bank Open Data: Access to electricity, rural (% of rural population) - Malawi - World Bank (World Bank)
Free and open access to global development data

World Bank Open Data: Ghana Data - World Bank (World Bank Data, 2019)

World Development Indicators | DataBank - World Bank

World Development Indicators | DataBank - World Bank

Cambodia Digital Education Inventory - World Education
A collection of digital tools and interventions that promote learning and teaching in Cambodia

Assistive Technology. Fact sheet. Retrieved 10 December 2020, from - World Health Organization

Deafness and Hearing Loss. Fact Sheet - World Health Organization (2017)
Deafness and hearing loss fact sheet from WHO: providing key facts and information on causes, impact, prevention, identification, management and WHO response.

Improving access to assistive technology, Report by the Director-General. - World Health Organization (2017)

World Inequality Database on Education - Viet Nam - World Inequality Database

Population of Cities in Vietnam 2024 - World Population Review

OER2Go - World Possible
The world's best educational websites, now available for download OER2Go Explore

RACHEL - World Possible (World Possible)
Hi, my name is RACHEL Buy online

Using Digital Content for Learning: Teacher’s Guide - World Possible

Vietnam Population (2024) - Worldometer - Worldometer (Worldometer)
Population of Vietnam: current, historical, and projected population, growth rate, immigration, median age, total fertility rate (TFR), population density, urbanization, urban population, country's share of world population, and global rank. Data tables, maps, charts, and live population clock

The impact of technology on a multilingual world: Problems and opportunities - Wu, A.; Gonsalves, S-L.R.; Wagner, D.A. (In Lubin, I. (Ed.), Translating Learning Ecologies: ICT Across Global Contexts.)

Research Guides: AI-Based Literature Review Tools: Home - Xiao, Daniel
Research Guides: AI-Based Literature Review Tools: Home
Keywords: _Added-ailr-2024